The Financial Evaluation of Amazon.com, Inc - Ao Ieong, Sio Tai (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Couple Satisfaction in Partners of Male Shift Working Pilots - Bredenhann, Andri (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

澳門青少年沉迷網絡遊戲之研究 - Chai, Chin (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

The Financial Evaluation of the Coca-Cola Company - Chan, Cheok Hei (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The Conservation and Restoration of Pith Painting: A Case Study of Five Art Pieces from Private Collections - Chan, Chi Leong (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph

The Financial Evaluation of the Estée Lauder Companies Inc - Chan, Hoi Ieng (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

澳門小學階段新入職教師在融合教育中的挑戰 =: Challenges Encountered by Newly Recruited Teachers in Inclusive Education of Primary Schools in Macau - Chan, Pan Pan (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

How Social Media Affects the Purchase Intentions of Female Consumers in Macao: Watching Beauty and Cosmetic Product Experience Videos on Youtube - Chan, Velda (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

臺灣地區融合教育政策與實施對澳門融合教育推行啟示之研究 - Chang, Hei Man (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

The Impacts of Burnout and Work Engagement on Performance: a Study of a Surveillance Team - Chang, Pou I. (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

澳門小學教師與資源教師合作現況與挑戰 - Chao, Cheng I. (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Look Before You Eat: An Augmented Reality Menu - Cheang, Ka Pui (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Design (MDG); University of Saint Joseph

The Financial Valuation of Nike Inc - Cheng, Kin San (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

不同社經地位之家長和教師對親師溝通的意見: 一間澳門幼稚園的個案研究 - Cheong, Man Hong (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

對於澳門特殊需求學生教育的體驗: 來自自閉症兒童家長的聲音 - Choi Chi Wai (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Education(MED); University of Saint Joseph

Rewriting Life Story and Career Development: a Case Study Using a Narrative Approach - Choi, Ka Lok (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The Financial Valuation of Starbucks Corporation - Chong, Cecilia (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Approaches to Customer due Diligence of Anti-Money Laundering Compliance of Banks in Macao - Couto, Miguel Angelo (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Biculturalism and Parenting Styles among Filipino Mothers and Young Adult Offspring in Macao - Doctor, Ana Catarina Alvarez (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

A Financial Valuation of Jacobs Engineering Group Inc - Encarnação, Bruno Miguel Arantes da (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

O trabalho de recuperação de crianças resgatadas do tráfico humano no Nepal=Recovery work for rescued children from human trafficking in Nepal - Espindola, Marcelo Gonçalves (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

探討澳門托兒所推行融合托兒服務的策略與挑戰 - Fong, Sou Lei (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Walking with John: the go-along as ethnographic tool to explore the lives of adolescents with autism spectrum disorder - Gnanaraj, Steffi (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Entry Into the Mainland China Market: a Case Study of Macau's Portuguese Wine Companies - Gonçalves, Daniela Filipa Atraca dos Santos (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The Impact of E-Commerce in Local Flower Consumers in Macao: Online Stores vs Physical Stores - Guerreiro, Diana Macedo (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

Smart Home Interactive Design: How can Interactive Design be Combined with a Smart Home System to help Human Future? - He, Min Yi (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Design (MDG); University of Saint Joseph

The Financial Valuation of Dunkin' Brands Group, Inc - Ho, Hon U. (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Effectiveness of Art Therapy for Children with Special Educational Needs - Ho, Weng Chong (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

澳門幼稚園教師對融合教育的態度 - Ieong, Leng San (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A Financial Valuation of Vitasoy International Holding's Limited - Iong, Sio Ieng (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The Effect of Peers, School Connectedness, Parents on Internet Gaming Addiction in Adolescents - Ip, Tan Long (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

A Study of the Management Style in Macau - Kong, Angela Maria (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

初探澳門初任幼稚園教師對融合教育生問題行為的處理方法及其心理狀態 - Kuan, Wai Leng (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Two Projective Drawing Tests as a Consolidated Measure to Identify and Understand the Underlying Problems of Primary Children with Emotional-Behavioral Issues of Concern - Kuok, Ka Lai (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Children's with SEN Views About Their Experience in Inclusive Education - Lai, Hoi Lam (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Community Participation of Cultural Heritage Management in a Rapid Growing Economy: A Case Study of Macao, China - Lam, San (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph

The Financial Valuation of Facebook, Inc - Lam, Weng I. (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

澳門融合生家長參與個別化教育計劃之現況分析 - Lao, Sin Ian (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Designing an Optimized Constructed Wetland System with Circular Sustainability for Wastewater Treatment in Macao - Lei, Micaela (University of Saint Joseph, 2020)
Keywords: Master of Environmental Sciences and Management (MESM); University of Saint Joseph

The Theory of Educational Curriculum of Confucius and Plato - Lei, Wai Seng (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Philosophy; University of Saint Joseph

Interactive bedside lamp design - Leong, Kit Teng (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Design (MDG); University of Saint Joseph

Analyzing Intercultural Romantic Relationships of Filipinos in Macao: Informing Counseling Strategies - Li, Anne Michelle Sia (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Hypnotherapeutic Treatment as a Way to Enhance Sleep Quality: Case Study on a Clinical Counseling Professional in Macao - Li, Hiu Yung (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The Role and Influence of External Stakeholders on the Corporate Governance Practices of Gaming Companies in Macao - Limbo, Lem Anne Agnas (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The Role of Sponsorship in Corporate Social Responsible Practice in the Macao Gaming Industry - Lo, Hoi Man (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The Status of Mangroves in Macao and the Efficacy of Localized Environmental Educational Intervention on School Students' Environmental Knowledge - Loi Hoi Kei (University of Saint Joseph, 2020)
Keywords: Master of Environmental Sciences and Management (MESM); University of Saint Joseph

Parenting Training for Enhancing Self-Esteem, Self-Efficacy, and Emotional Regulation of Mothers Who Were Victims of Domestic Violence - Lou, On I. (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

澳門合作學習實踐情況: 一所小學的個案研究 - Lou, Wai Leng (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

An Analysis of Teachers' Perceptions of Professional Development Activities in Macao: A Mixed Methods Study - Ma, Babolal Choi I. (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Education(MED); University of Saint Joseph

Family Life Cycle and Number of Children in A Family Affecting Parent’s Parenting Style, Parental Stress, Life and Marital Satisfaction - Mak, Chong Hin (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Enhancing Sustainability Development in Macao Through a Green Educational Program: An Action Research Study - Martins, Cíntia Pacheco Leite (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Quality of Life and Wellbeing of the Foreign Communities in Macao - Mohr, Silvia Isabel (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The Social Welfare Services of the Diocese of Macau in the 20th Century: The Macau Cooperation Model of Social Welfare Work - Mou, Chi Chong (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph

Seeing the True Self: A Comparison of Arthur Schopenhauer and Japanese Zen - Ng, Fong Man (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Philosophy; University of Saint Joseph

澳門數學教師學科教學知識之個案研究 - Ng, Ka Io (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Preservation and Rehabilitation of Macao Industrial Heritage: A Case Study of the Iec Long Firecracker Factory - Ng, Kit Leng (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph

Teacher Burnout: Applying the Job Demands and Resources Model in Macao - Ng, Kun Keong (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Teachers' Approaches to Ethical Dilemmas in Catholic Schools - Ngo, Van Thu Giang (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

How does Fake News Affect People in Asia & Europe During a Pandemic? A Case Study About Macao and Portugal - Nicolau, Claúdia de Almeida Henriques (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

Caregivers of Persons with Neurodevelopmental Conditions: Understanding Their Perspectives of the Need of Clinical Counselling Intervention - Pagdanganan, Paula Ramos (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Macau Mobility: Empowering the Commuter in Partial: Case study: E.Mobility Application - Pereira, Julieta Soares Gomes (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Design (MDG); University of Saint Joseph

A Financial Valuation of 3M Company - Poon, Hung Kong (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Exploring the Distinctive Identity of Catholic Education in Three Catholic Secondary Schools in Macau - Ribeiro, Daniel Antonio De Carvalho (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

The Trend and Characteristics of Deviant Behavior of Young People in Macao Between 2001 and 2019 - Sam, Lek I. (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

Risk Analysis in Sustainable Buildings' Construction Projects: A Perspective from Macau and Hong Kong - Santos, Eduardo José Piteira Paulo dos (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Unequal Access to Shadow Education in South Korea: Selection Processes of Parents from Different Socio-Economic Statuses - Seok-Hoon Jeon (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

探討澳門及香港華德福學前教育的實踐: 來自教師的視角 - Sio, Ka I. (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

The Role of Parents in the Referral Process to Inclusive Education in Macao - Tam, Ka In (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

澳門小學資源教師的工作壓力及其應對方法之個案研究 - Tam, Lai Si (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Macau Sound Gallery: Soundscapes of Macau An Immersive Interactive Installation - U, Chin Cheng (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Design (MDG); University of Saint Joseph

The Development of Brand Equity in the Five-star Hotel Industry of Macao - U, Weng I. (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The History of Macau’s Portuguese Radio Case study of the first thirty episodes of the programme Frequência Académica - Vidinha, Margarida Sajara (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

A Content Analysis of School Bullying: A Review of Macau Newspaper Reports - Vong, Fan Nei (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Post-Divorce Parent-Child Relationships Impacts and Coping Mechanisma: Qualitative Study In Macao - Vong, Iek Chong (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Place Marketing: Macao as the Art City for the Future Direction - Wong Ka I (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

Socio-economic Impacts of Low Unemployment in Macau - Wong, Leng Cheng (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Human-Belongings Behaviour Analysis: A Smart Interactive Cabinet - Wong, Nga Ieng (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Design (MDG); University of Saint Joseph

A Financial Evaluation of Walmart Inc - Wong, Sut Man (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Green Space in Macau: Comparative Analyses and Suggestions for New Reclamation Areas - Xiao, Yuan Bin (University of Saint Joseph, 2020)
Keywords: Master of Environmental Sciences and Management (MESM); University of Saint Joseph

'Being at Leisure' as a Primary Element of Pilgrimage: A phenomenological study of the Distinction between Christian and Secular Pilgrimage - Yuan, Haojun (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Philosophy; University of Saint Joseph

運用音樂遊戲增進幼兒情緒調節及人際互動之行動研究 - 張麗嬋 (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

以行動研究探討遊戲學習對小學三年級學生數學問題解決能力之影響 - 曾威遠 (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Education(MED); University of Saint Joseph

澳門小學中文科基本學力要求的實施現況研究: 個案研究 - 鄧樂怡 (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

探討澳門中學生學習困難、師生關係及學習動機之個案混合研究 - 陳思匯 (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Single-Use Plastic Assessment in Macau Hospitality Industry: Bottled Water as a Case Study - Ao Ieong, Kin San (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Environmental Sciences and Management (MESM); University of Saint Joseph

Movie Censorship – A Legitimate Tool or a Dictatorial Technique - Borges, Rui Carlos Moura (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

Father’s Involvement and Parenting Styles in Macao - Chan, Ieng Chong (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Existential Psychotherapy and Irvin D. Yalom’s Perspective: A Systematic Literature Review - Chan, In Leng (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Interaction Design for a Contemporary Learning and Teaching Environment: Promoting Independent Learning at the Primary Level - Chan, Ka Chi (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Design (MDG); University of Saint Joseph

Influence of Parenting Styles Across Generations in Chinese Families in Macao - Chan, Lai Teng (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

IoT Application into Macau Secondary School - Chan, Long Wai (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Design (MDG); University of Saint Joseph

A Financial Valuation of Alibaba Group Holding Limited - Chan, Man Hong (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Family Support, Job Insecurity, Coronavirus Stress and Leadership Styles Effects on Burnout and Work Engagement in Hospitality during Covid-19 Pandemic in Macau - Chang, Pou I. (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph

Modular 3D-Printed Tangibles for Children’s VR Toys - Chau, Iok Fong (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Design (MDG); University of Saint Joseph

The Understanding and the Attitudes Toward Life Education Among Macau Citizens: A Case Study - Che, Iok Seng (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

澳門幼稚園老師在融合教育班級經營中面對的挑戰 =: The Challenge of Managing Inclusive Education Classrooms Faced by the Kindergarten teachers in Macau - Cheang, Hoi Son (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Examining the Itinerant Support Teachers’ Program in the Implementation of Inclusive Education in Macau - Cheang, Mei Chan (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

The Mediation Effect of Organisational Commitment on Job Autonomy and Turnover Intentions - Cheong, Lai Ieng (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph

A Comparative Study of Sympathy in David Hume, Karuna in Buddhism, and Ren in Confucianism - Chon, Iao Pang (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Philosophy (MPH); University of Saint Joseph

An Investigation on the Effectiveness of Enhancing Public Relations Through the Use of Facebook by the Public Sector of Macau - Chong, Chan U. (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

Parents’ Experiences in Macau: From Assessment to Inclusive Placement for Children with SEN - Estadieu, Karine Anne Marie Thepot (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

澳門特殊教育教師助理員的工作現狀與工作滿意之探討: 基於質性之實踐分析析 - Fong, I. Mei (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

澳門小學常識科教師在融合生班級上運用 STEM 教學方法之研究 =: Human-Belongings Behaviour Analysis: A Smart Interactive Cabinet - Fong, Sao Hong (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

An Exploratory Study into How the Application of Neurosciences can Assist in Understanding the Decision-Making Process Under Stress - Furtado, Filipa Magalhães de Moura e Mota (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Continuing Education in Macau: The Meanings and Experiences of Students Pursuing a Master’s Degree - Gil, Sofia do Carmo (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A Study of Social Enterprises in Macau: The Contributing Factors to The Development of Hybrid Social Enterprises - Hau, Pak Kei (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

澳門幼兒園教師對推行美感教育的態度=Kindergarten Teachers’ Attitudes Towards the implementation of Aesthetic Education in Macau - Ho, Ka Kio (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

The Mediating Role of Empathy on the Impact of Perceived Parenting Styles on Prosocial Behaviors of Adults - Hoi, Mei Pui (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

A Financial Valuation of Marriott International, Inc - Ian, Kin Wai (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Culture, History, and Hospitality Public-Private Partnership of the Gaming Industry and the Macau SAR Government in the Cultural Tourism /Natural Kou, Chi In - Kou, Chi In (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph

The Effect of Temporal Variation in Noise Exposure on Hearing and Inner Ear in the Zebrafish Model - Kuan, Chi Kin (University of Saint Joseph, 2021)
Keywords: Master of Environmental Sciences and Management (MESM); University of Saint Joseph

Parental Involvement and Child Development in Macao: Association with Family Income, Parental Education and Working in the Gambling Industry - Kung, Hang I (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Classroom Interior Design and Creativity: The Contribution of Multifunctional Furniture for Higher Education Institutions in Macau - Kuok, Wai (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Design (MDG); University of Saint Joseph

An Evaluation of the Treasure of Sacred Art of St. Joseph’s Seminary - Kwak, Maria Sheli (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph

Nostalgia in Flux From the Perspective of Chinese Jia and Heidegger’s Heimat - Lai, Tong Chon (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Philosophy (MPH); University of Saint Joseph

Mangroves as a Nature-Based Solution for Coastal Water Eutrophication in Macao Sar China - Lai, Wai Ian (University of Saint Joseph, 2021)
Keywords: Master of Environmental Sciences and Management (MESM); University of Saint Joseph

Why did Uber Fail in Macau? Causes and Consequences of a New Digital Business Model Application - Lai, Weng Ian (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

澳門教師專業發展研究 –基於《非高等教育私立學校教學人員制度框架》的政策分析 - Lam, Iek Fei (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

澳門融合教育教師專業培訓與融合教育發展路向之研究 - Lam, Kin Ian (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

澳門普通幼兒家長對融合教育的態度 =: Attitude of parents with regular childern towards inclusive education in Macau - Lam, Ngai Meng (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

澳門普通教師對融合教育的信念和實踐經驗: 一間融合教育資助計劃之幼稚園的個案研究=Macau Ordinary Kindergarten Teachers’ Belief and Practical Experience in Inclusive Education: A Case Study of a Kindergarten that Has Just Joined the Inclusive Education Funding Scheme - Lao, Cíntia da Rosa (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

The Association Between Early/ Emerging Adult-Parent Attachment and Problematic Internet Use Among College Students in Macao - Lao, Sio Mei (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The Caluation of Microsoft Coproration - Lee, Ka Lou (University of Saint Joseph, 2021)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The Study of the Valuation of ManpowerGroup Inc - Lei, Choi Ieng (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Act as Animal in Virtual Reality - Leong, Chi Hoi (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Design (MDG); University of Saint Joseph

Oligopolistic Strategies in the Gaming and Hospitality Industries of Macau - Leong, Chi Leng (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

An Exploration of Building Up the Quality Parent-Child Relationship in Childcare Service in Macao - Leong, On Na (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

A Study on the Educational Policy Reform Implementation of ''The Requirements of Basic Academic Attainments'' in Early Childhood Theme Teaching Curriculum in Macau =: 澳門幼兒教育在主題教學課程實行教育政策改革「基本學力要求」之研究 - Lin, Hou U. (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Attitudes, Acceptance, and Registration toward Organ Donation in Macao - Lou, Kin Heng (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Corporate Social Resopnsibility Practices in Macau - Marcelo, Nicole Chantal Clemente (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Employee Motivation in Social Enterprise: The Case of Caritas Elderly Care Services in Macau - Mui, Un Kei (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Green Roof Application in Macao SAR - Noblesala, Marco Paulo R. (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Environmental Sciences and Management (MESM); University of Saint Joseph

Study and Analysis of English Press in Macau: Its Impact and Challenges - Pangan, Cheila Alexis Clemente (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

How Do Chinese Manufactured Products Affect Purchase Intention in a SAR of PRC? The Case of Macao - Silva, Márcio Rossano Pegado da (University of Saint Joseph, 2021)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A Study of the Perspectives and Experiences of Macau Secondary School Students with Special Education Needs in Inclusive Education - Sio, Man Cheng (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Parental Stress and Family Relations in Macao: The Mediating Role of Parenting Styles - Siu Kuan Lei (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

O Autoconceito no Pré-Escolar em Contexto Educativo Multicultural e Plurilinguίstico=Preschool Children’s Self-concept in a Multicultural and Multilingual Educational Context - Sousa, Joana Luísa Dourado de (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

探討澳門輟學生經歷之研究 =: A Qualitative Study on the Experiences of School Dropouts in Macau - Tam, Sok Man (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Positive Approach in Preventing Depression in Adolescents: Comparing Local Chinese and Filipino Migrant Adolescents in Macao - Tejada, Anali Jane Gabala (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Development of Cultural Tourism in Macau through the Visual and Performing Arts - Tique, Ana Teresa Leal (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

An Exploratory Study of Factors Influencing the Consumer Behaviour of Macau Chinese Millennial Women in their Purchasing on Taobao - Tong, Ka Wai (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Experiences and Reflections Related to Mental Health Among University Students during Covid-19: A Case Study - Tou, Un Ieng (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The Role of Cognition as a Mediator for Narcissism and Trait Aggression as Predictors of Aggressive Driving Behavior - Van, Hou Wai (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The Roles and Functions of Social Worker Within Crisis Management of the Pandemic COVID-19 in Long-Term Care Facilities of Macau: A Case Study - Wong Oi Lin (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

Social Integration and the Screening of the Early-Stage Dementia in Older Adults: The Mediation Role of Mental Health - Wong Wai Hong (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

認知情緒調節策略在澳門家長的童年創傷經驗與專制式教養模式之間的中介作用 =: Childhood Trauma on Authoritarian Parenting among Macao Parents: The Mediating Role of Cognitive Emotional Regulation Strategy - Wong, Ka Kei (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Impact of Vessel Traffic on Underwater Soundscape and Marine Mammals in the Pearl River Delta - Wong, Man Ieng (University of Saint Joseph, 2021)
Keywords: Master of Environmental Sciences and Management (MESM); University of Saint Joseph

澳門小學教師性別意識與實踐性別平等教育的研究 =: A study on gender consciousness and practice in gender equality education of primary school teacher in Macau - Wong, Nga Lam (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Exploratory Study of a Postpartum Confinement Centre: An Adaptation of Emerging Practice in Macao, SAR - Wong, Wai Sam (University of Saint Joseph, 2021)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The Experience of Happiness: Grasping Bliss through Buddhism and Kierkegaard’s Existentialism - Wu, Wai Han (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Philosophy; University of Saint Joseph

A Case Study on Using House-Tree-Person (HTP) Projective Drawing Technique to Identify the Personality Traits of Children with Socio-Emotional Challenges - Yee, Seong Wa (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Study of management style in Canada - Ao, Ka Chon (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Maternal Postpartum Experience in Macao: The Relationship Between Demographics, Income, Social Support and Postpartum Depression - Bonthuis, Ana Maria Barradas Leitão Abril (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

A Study of the Macau personal data protection legal regime - Cabanos, Leilani Oliver (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Lusophone and International Public Law(MLIPL); University of Saint Joseph

How Might We Provide Students with Agility and Digital Literacy? Case Study of the Bachelor of Communication and Media at the University of Saint Joseph - Cathagne-Benventi, Sophie (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

A study on Children's Learning Evaluation in Macao Kindergarten——Taking a Kindergarten in Macao as an example =: 澳門幼師對幼兒學習評量之研究——以澳門某幼稚園為例 - Chan Ka Man (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Factors Influencing Disability Inclusion Practice in Social Media: A Case Study of MDA Service Centre for the Deaf - Chan Wai Peng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

A Study on the Relationship Between Positive Emotions and Work Stress in Private Kindergarten Teachers in Macau=: 澳門幼稚園教師正向情緒與工作壓力關係之研究 - Chan, Hio Tong (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Till Death Do (Not) Us Part: Elderlies’ Preparation on Wealth Transmission and the Effectiveness of Testaments in Macao - Chan, Hong Kei (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Community Development (MCD); University of Saint Joseph

The Perception of Skirt Wearing and Masculinity in Contemporary Society: A Case Study in São Paulo, Brazil and Shanghai, China - Chan, Jose Manuel Enesoe (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

Project-based Learning in the Subject of General Studies in a Grade Five Class: A Case Study Approach - Chan, Ka Ho (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

澳門戲劇教育發展的演變及挑戰: 以澳門演藝學院戲劇學校為研究對象 =The Growth and Challenges of Theatre Education in Macau: A Case Study of The School of Theatre at the Macao Conservatory - Chan, Ka I. (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph

Online Gaming with Digital Currencies: A Comparative Legal Study - Chan, Ka Yuen (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Lusophone and International Public Law(MLIPL); University of Saint Joseph

Work-Life Balance and Life Satisfaction in Macao: The Mediating Effect of Work Satisfaction - Chan, Lok Man (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Counselling and Psychotherapy (MCP); University of Saint Joseph

A Qualitative Research on Tutors' Attitudes Towards the Implementation of the Emotional Eduation in Macau Nurseries =: 澳門托兒所導師對幼兒情緒教育態度的質性研究 - Chan, Man Leng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Experience the Past in the Present with Immersive Technologies Case Study: “The Old Ladies’ House”, Albergue, Macau - Chang, Tin Lan (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Design (MDG); University of Saint Joseph

An Investigation on Macao Children with ASD and their Families needs on Social Support - Chau, Chin Fong (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

澳門新入職教師在融合教育的學校中面對的挑戰 =: New Teachers' Challenges in School Which Provided Inclusive Education in Macao - Che, Ka Ian (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Park-meter: Designing an Innovative Macau System - Cheang, Chi Tat (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Design (MDG); University of Saint Joseph

從混合性研究中探討澳門長者對睡眠健康認知及其相關之因素 =: Exploring Perception on Sleep Health and its Related Factors among Older People in Macau - A Mixed Methods Study - Cheang, Ka Leng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

How Does Employer Brand Affect Employer of Choice? A Case Study of Two Macau F&B Groups’ Employer Branding Comparisons - Chen, Zhi Yi (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

初中教師面對融合學生校園欺凌經驗及應對策略之研究 =: Research on the Experience and Coping Stratrgies of Junior High School Teachers in the Face of Integrated Students' Bullying in Schools - Cheok, Pou Weng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Mandatory Provident Fund Scheme: Prespectives of Macau Employees - Cheong, Kit I. (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

The Relationship Between Stress and Emotion Regulation with Students’ Academic Achievement - Cheong, Sin Teng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

An Investigation into Play-Based Educational Support For The Developing Social-Communication Skills in Children with Autism Spectrum Disorder (ASD) in Kindergarten - Cheong, Tânia Guilherme (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Palate Consciousness: A Philosophical Analysis on the Cultivation of Gustatory Aesthetics Through the Framework of Phenomenology of Perception - Chiang, I. Man (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Philosophy (MPH); University of Saint Joseph

Unity of Knowing and Acting from Christian and Confucian Ethical Practices: An Exegesis of Mark 4:1-20 - Chiang, Sau Kuan (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Philosophy (MPH); University of Saint Joseph

Redefining Macau's Film Industry: Case Studies on local Film Marketing & Distribution - Choi Chi Cheng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

The Application of Zhuangzi's View on Death to the Philosophical Counselling - Choi, Cheng In (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Philosophy (MPH); University of Saint Joseph

An Action Research on the Influence of Flipped Classroom on Learning Achievement and Learning Motivation of Primary School Students in Programming Courses=: 翻轉教學對於小學程式設計學習成效與學習動機影響之行動研究 - Choi, Wan Chong (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Knowledge and Attitude of Parents with Regular Primary Children Towards Inclusive Education in Macau =: 澳門小學普通生家長對澳門融合教育的認識及態度之調查報告 - Chong, Leng Leng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

E-Commerce in the Hospitality Industry: The Online Hotel Booking and Digital Marketing in Macau - Chowdee, Nattiya (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

Perspectives and Practices of Macau Secondary School Teachers Regarding ICT in Teaching and Learning - Das, Amit (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Clothing and School Uniforms in Macau: Maria João Nunes Das - Das, Maria João Nunes (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Exploratory Case Study of Teacher's Perspectives in Assisting Students with Special Needs in Inclusive Schools in Macau - Diakité, Patrícia Dina Correia Silves Ferreira (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

澳門年輕群體對性別多元態度與態度構成因素之研究 =: The Attitude of the Relative Influential Factors and Gender Diversity on Youth in Macau - Fion, Si Wai (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

Art-Based Intervention For Children with ADHD: Catina Fong Chi Cheng - Fong Chi Cheng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Expansion of private tutoring centers in Macau: voice from parents of primary school students - Fong, Chan Seng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

合作學習法在小學中文科教學中的實施: 以澳門某小學為例 = The Implementation of Cooperative Learning in Primary School Chinese Teaching: A Case Study of a Primary School in Macao - Fong, Hio Man (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A Study on inclusive Class Management by Nursery Teachers in Macau =: 澳門托兒所融合班教師班級經營之研究 - Fong, Ka Lei (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

The Moderating Effect of Job Alternatives Perceptions in the Relationship Between Burnout and Turnover: A Study During the COVID-19 Pandemic in Macao - Fong, Sut Cheng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph

Macau's Historical House Taxonomy: The Shophouses at the Rua de Cinco de Outubro (Case Studies) - Fu Ho I (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph

The Association Between Interpersonal Relationships and Mental Health in College Students in Macao - Guo, Peiling (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

澳門已婚人士的婚姻質量與社交媒體參與之研究 =: The Study of Marital Quality and Social Media Engagment Among Married People in Macau - Ho, I. Mei (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

The Influence of Official Digital Infographics in Macao during the COVID-19 Pandemic - Ho, Weng In (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

A STUDY OF PRIMARY SCHOOL TEACHERS' TEACHING PROBLEMS AND THEIR COPING STRATEGIES FOR TEACHING INCLUSIVE STUDENTS IN MACAO =: 澳門小學教師面對融合學生的教學困擾及其因應策略之研究 - Hoi Ka Cheng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

The Indirect Effect of Job Insecurity and COVID-19 Induced Stress on Mental Health through the Mediating Effect of Burnouts and the Moderating Effect of Perceived Social Support among Macau Gaming Employees - Hoi, Lok (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

A Study on the Peer Relationship of Students Aged 9-12 with Special Educational Needs in Macao=: 澳門九至十二歲融合生與同儕關係之研究 - Hong Mei Na (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

General Teachers’ Attitude Towards Inclusive Education in Students with Dyslexia in High School Students=: 中學普通班教師對患有讀寫障礙學生的認識與其融合教育的態度 - Hong, Yufang (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

An Action Study of Using Game-Based Learning into English Learning to Improve the Lerning Outcomes of Primary Level Students in Macau =: 遊戲式教學融入澳門小學低年級英語課程以提升學生學習成效之行動研究 - Hsu, Hsiao Chien (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

New Great Learning Oneness Epistemic Model for the Greater Peace: A Philosophical Analysis on the Concept of Oneness and its Application with Veganism - Hun, Kuong U. (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Philosophy (MPH); University of Saint Joseph

A Qualitative Exploration of the Learning and Teaching Experiences of Teachers Who Completed A Post-Graduate Early Childhood Diploma in Macau =: 探討澳門學位後幼兒教育文憑教師的學習體驗及其教學實踐之質性研究 - Ieong, Weng Ian (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

初探澳門更生人士在專業工作過程的成功因素=: Explore Successful Factors in Recognition of Professional Work Process for Ex-Offenders - Ip, Ka I. (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

Lighting Up A Place with Good Stories: Heritage Interpretation Strategies and the Macau Historic Centre - Ip, Kin Man (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph

An Analysis of Celebrities and KOLs Influence Consumer Decisions on the Luxury Fashion Market in Macau - Ip, San U. (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The Influence of Strengths-Based Intervention to Students’ Engagement and Self-Efficacy in Macau - Jr. Tabilas, Faustino T. (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Counselling and Psychotherapy (MCP); University of Saint Joseph

Problematic Internet Use and Subjective Wellbeing Among University Students in Macao - Kam, Chi Fat (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

澳門普通學校教師任教融合生的教學困擾和支援服務需求之研究=: A Study of the Teaching Distress and Needs of Supportive Service of Students with Special Educational Needs Taught by General School Teachers in Macau - Kong, Chi Fong (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

澳門新任教師職業適應的研究：: 來自在內地與澳門接受師範培養的幼兒教師反饋= Research on the Career Adaptation of New Teachers in Macao Feedback from Kindergarten Teachers who Received Teacher Education in the Mainland and Macau - Kou Mei Kei (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Use and Perception of Visual Communication on Instagram by Macau Residents - Ku, Kit Mei (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

Fintech Services in Guangdong-Macao in Depth Cooperation Zone in Hengqin: An investigation of Macao Users' Adoption - Kuan, Chi Hou (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Using Online Learning to Enhance Motivation in an English as a Second Language Classroom: An Action Research Study - Kuok, Weng Kei (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A Qualitative Research on The Career Choice, Current Situation and Prospects of Preschool Tutors Working in Nursery Schools and Kindergartens in Mainland China, Taiwan and Macau=: 中國內地、台灣、澳門幼兒導師從事托兒所和幼兒園工作的職業選擇、現況和前景之質性研究 - Lai Ka Wai (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Exploring the Problems and Strategy Use by Primary School Teachers in Conducting Classroom Management Under the Policies of Inclusive Education in Macau =: 探討澳門融合教育政策下小學老師面對班級經營的困難及策略 - Lam Cheng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Illegal Immigration and Population Police in Macau: A Case Study of Fujianese Immigrants = 澳門非法移民問題及其治理——以澳門的福建移民為例 - Lam Lai Teng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph

Intention Towards Online Counseling among Service Provider in Macau=: 澳門社會服務提供者對應用線上輔導的意向 - Lao, Hoi Keong (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

The Impact of Father-Adolescent Relationship on Child Development in Macao - Lao, Pak Lun (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Classroom Supports For Primary 5 to Form 3 Students with Emotional and Behavioural Challenges: A Case Study Approach - Lao, Pek Weng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

澳門長者對樂齡科技的感知及應用動機研究 =: Elderly's Perception and Motivation for the Application of Gerontechnology in Macau - Lee, Hou Sun (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

探討透過「五感教學」進行幼兒社交情緒教育之行動研究 =: Action Research on Teaching the Social Emotion in Children by Using on Five-Senses Teaching Approach - Lei Weng I (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Virtual Meetings: How to Increase Communication Effectiveness - Lei, Chio Lan (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

Exploring Teachers' and Students' perceptions in Formative Assessment Through Project-based Learning for Students Included in Mainstream Schools - Lei, Lei Peng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Exploring Teachers' Experiences and Perceptions of the Use of the IEP with Students with ASD in Primary Schools - Lei, Mei Seong (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Parental Perspectives on Inclusive Education in Macau - Leong, Ka Man (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A Study of the Professional Development of Mid-High Level Management Personnel of Non-Tertiary Education in Macau=: 澳門非高等教育中高層管理人員專業發展之研究 - Leong, Ka Na (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A Financial Valuation of Under Armour - Leong, Ka Wa (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Moral Self-Regulation or Consistency: The Role of Cultural Values and Workplace Status - Leong, Kin Hei (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph

The Financial Valuation of Waste Management, Inc: Daniela Wai Ka, Leong - Leong, Wai Ka (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The Financial Valuation of Walmart Inc - Lestro, Gonçalo Nuno das Neves Arrojado (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

An exploratory study of Macao's role as arbitration seat for commercial disputes between China and portuguese-speaking countries - Leung, Cheok Si (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Lusophone and International Public Law(MLIPL); University of Saint Joseph

澳門幼稚園融合教育專責團隊合作模式之探究 =: A Study on the Cooperation Model of Kindergarten Inclusive Education Collaborative Team in Macau - Li, Xiao Hua (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

To Identify Buyer Behavior Towards Online Shopping Due to Covid-19 Pandemic in Hong Kong - Lio, Cheng Tong (University of Saint Joseph, 2022)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

澳門小學教師經營融合班級的困擾與特教專業知能之關係研究 =: The Relationship Between Teachers' Difficulties in Operating Inclusive Classes and the Professional Competence of Special Education in Macao Primary Schools - Lo Ka Chon (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

探討第29/2020號行政法規對特殊教育教師為特殊需求學生評估的影響 =: Exploring the impact of Administrative Regulation No. 29/2020 on the evalution of the special education teachers for students with special needs - Lo, Chon In (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

澳門中年男士焦慮狀況、求助態度與自殺意念之相關研究 =: A Correlational Study Between Anxiety and Help-Seeking Attitudes on Suicidal Ideation of Middle-Aged Men in Macau - Lo, Kuan U. (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

The relationship between social support and death anxiety among elderly living alone in Macao - Lo, Pou Leng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

LIFE CYCLE ASSESSMENT OF CONSTRUCTED WETLAND SYSTEMS FOR TOURISM UNITS WASTEWATER TREATMENT - Lo, Weng In (University of Saint Joseph, 2022)
With water being an essential for life on Earth, it is vital to preserve it and regenerate it, in order to be available for a myriad of uses. Though many types of wastewater management and treatment are available, most rely on high energy input and are therefore not ideal for many circumstances. Constructed wetlands (CW) are an alternative nature-based solution to be applied to wastewater treatment. This study undertakes a Life-Cycle Assessment (LCA) of a CW as a means of wastewater treatment and aims to understand how these systems can be an environmentally conscious alternative. The CW under study is located in a rural mountain area in the north of Portugal. Receives wastewater from a tourism unit and operates with horizontal subsurface. The LCA analyses the CW through the construction, operation (treatment), and composting phases. This approach allows the entire scope of the life cycle to be included, of which, the composting phase has been absent in similar LCA previously undertaken. Analysis focuses on the impact categories: Ozone Layer Depletion Potential, Global Warming Potential, Acidification Potential, Eutrophication Potential and Human Toxicity Potential. Of the five categories, none increase during the treatment phase, and indeed, Acidification Potential, Eutrophication Potential, and Human Toxicity potential all decrease. Ozone Layer Depletion Potential and Global Warming Potential increase significantly during the construction and composting phases respectively. Both can be rationalized, with the former being a result of heavy diesel machinery use in construction and the latter a natural byproduct of composting. The results are net positive and display the ability for CW as a low energy wastewater treatment which can limit environmental impact by choice of construction and composting methodology
Keywords: Lifecycle assessment; Master of Environmental Sciences and Management (MESM); University of Saint Joseph; constructed wetland; wastewater treatment

Exploring Current Collaboration Practices of Regular and Resource Teachers within Inclusive Education: An Analysis of Teacher Perspectives - Loi, Sio Wai (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Career Development of People with Physical or Sensory Impairments in Macau - Ma I Mei (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

Influencer Industry Development in Macau: Case Study about Social Media Influences in Macau - Madan, Roberto (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

The Influence of Online Payment Methods on Consumers’ Online Purchase Behavior: The Case of Young People in Macau - Martins, Maria Cordes Aniceto (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Exploring The Influence of Culture on Parents’ Attitudes Towards Inclusive Education in Macao - Moreira, Irene Mitsiko Sadoyama (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

The Future of Cosmetics Marketing Strategy: An Exploratory Study into How Neuromarketing Can Deepen its Understanding - Neto, Andreia Da Conceição (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Teacher Efficacy: Inclusive Practice to Support Learning English as a Foreign Language (EFL) among Chinese-Speaking Students with Dyslexia in Macau - Oksana, Zorina (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Job Satisfaction, Dilemmas and Causes of Hearing Impaired People in Macau =: 澳門聽障人士工作滿意度、困境及其原因 - Pang, Wan I. (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

A Study of Primary School Students’ Motivation to Learn English as a Foreign Language in the Context of Content and Language Integrated Learning (CLIL) – A Case Study - Pau Ka Kei (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Exploring Differentiated Teaching in Primary Mathematics Classes in Macau - Pearce, Josef Nicolai (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

澳門唐餅文化研究 = A Study of the Culture of Traditional Chinese Pastry in Macau - Pong, Chio Fai (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph

Teachers’Perceptions of Performance Appraisal in a Secondary School in Asia: A Case Study - Potger, Matthew Rodney (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Environmental Education in Macau’s Schools: A Case Study on Teachers' Perceptions of Experiential Pedagogies - Reh, Paul Thu (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A Financial Valuation of Realty Income Corporation - Rodrigues, Ricardo David Almeida Fernandes (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Crisis Management – Dystopic Scenario VS Real-World Pandemic: The Case of Saramago’s Blindness that Anticipated the Initial Managerial Approach to Covid-19 Pandemic Taken by Unprepared Governments Worldwide - Rouxinol, Hernâni Tiago Caveirinhas (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Analysis of the Impact of Environmentally Sustainable Practices on Macau Hotels Guest Engagement - Santos, Ana Sofia Kong (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The Impact and Attitude of Urban Renewal on Citizen Residents in Macau - Si Cheng Iok (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

A Psychological and Phenomenological Analysis of Chinese People Who Are Not-Capable-Of-Saying-No - Song, Sok Fong (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Philosophy (MPH); University of Saint Joseph

Feasibility study of a Glamping Business in óbidos, Portugal - Sousa, Eugénio Ricardo de (University of Saint Joseph, 2022)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A Study of the Macau Personal Data Protection Legal Regime - Sun, Wai Lon (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Assessment of Methodologies Employed by Change Agents in Managing Organizational Change: A Case Study in the Hospitality-Gaming Industry - Tagulao, Thea Clarice Saavedra (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

街舞在澳門的在地化的研究1980-2020=: Localization of Street Dance in Macau 1980-2020 - Tai, Chou Wai (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph

The Effects of an Aikido Based Psychological Intervention Program in Workplace Stress - Tam, Heng Kun (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Children's Learning Interest and Social Interaction Through Play: An Action Research Case Study in A Pre-School in Macau= 運用遊戲活動增進幼兒學習興趣與社交互動之行動研究 - 以澳門一幼兒班為例 - Tang Pui I (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Motivations of preservice teachers: a case study on career changers to teaching in Macau - Thang, Tony Mana (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A Financial Valuation of Netflix, Inc - Tong, Si Weng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Exploring the Application of Online Learning Environment in the Teaching and Learning of Chinese in Elementary Education Sector in Macau=: 探討網上教學摸式在澳門小學中文科教與學的應用 - U Ka Weng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

澳門融合教師職業壓力來源研究: 以澳門某私立小學教師為例 = Occupation al Stress sources of inclusive education teachers in Macau - A study on primary shcool teachers in a private school - U, Ka Chon (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A Research study on the relationship between work stress and well-being of primary school teacher in Macau =: 澳門小學教師的工作壓力與幸福感之相關研究 - U, Ka Wai (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Enhancing Secondary Students' English Language Skills and Engagement through Cooperative Learning: An Action Research Study - U, Tat Si (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Integrative Educational Platform Focusing on Steam Approaches: A Macau Case-Study - Un Man Cheng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Design (MDG); University of Saint Joseph

Applying Social Skills Improvement System Intervention Guide to Primary Students with ADHD and Problem Behaviors in Macau: A Case Study - Ung, Hou Cheang (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Counselling and Psychotherapy (MCP); University of Saint Joseph

The Relationship Between Work-Life-Balance and Burnout: Effect of Gender and Sector of Activity - Vai, Han Kuoc (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph

Relationship Between the Academic Achievement and Extra-curricular Tutoring of Primary Students: Perspectives From the Parents = 課外補習與小學生學業成績之間的關係—-來自家長的視角 - Vong, Sok Kuan (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Exploring Macau Instagrammers’ Motivation for Using Instagram Story - Wong, Choi I. (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

澳門露宿者服務社工在新冠疫情情間的工作與挑戰 = The Opportunities and Challenges Facing Macau Social Workers Who Work with Homeless People During the Pandemic of 2020 : A Case Study - Wong, Choi Leng (University of Saint Joseph, 2022)
Edition: The Opportunities and Challenges Facing Macau Social Workers Who Work with Homeless People During the Pandemic of 2020
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

Perception About Challenges and Opportunities of Social Enterprise in Macau - Wong, Chong Chio (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Community Development (MCD); University of Saint Joseph

A Study on Spiritual Well-Being of Secondary School Teachers in Macau - Wong, Kuan Cheng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Parental Stress and Marital Satisfaction in Macao: The Mediating Effect of Parental Involvement - Wong, Pek Ieng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The Effects of Family Support, Friends Support, Supervisor Support, Co-worker Support, and Organizational Support to Resilience and its Effects to Work Engagement - Wong, Sio Peng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph

澳門普校教師對融合生的認知印象及接納態度之研究 =: A Study of Teachers's perceptions of cogitve impressions and aceptance attitudes on inclusive students in Macau - Wong, Tong Cheong (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

The Effect of Organizational Justice on Work Engagement Between Foreigner and Local Workers in Macau: The Moderating Effect of Organizational Commitment - Wong, Wai Fai (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph

CASE STUDY ON ART INTERVENTION WITH CHILDREN WITH AUTISM SPECTRUM DISORDER - Wu, Hoi Pio (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The Challenges of Nursery Teachers in the Early Childhood Inclusion Classes: A Qualitative Study of Macao Nursery Teachers - Wu, Ma Lei (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

澳門大學生在內地的就業意向及其影響因素調查=: A Study on Macau Undergraduate Students’ Working Intention in Mainland China - Wu, Zhi Ying (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Self-perception of primary students with dyslexia in Macao =: 探討澳門小學讀寫困難融合自我探索學習現況及挑戰 - 何素儀 (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

The Impact of Macau Teaching Professionalism to Kindergarten teachers' Occupational Identity and Competency: A Study on In-service Teachers' Perception = 澳門教師專業化對幼兒教師職業身份認同和勝任感的影響：來自在職教師的看法 - 張翟 (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

運用正念呼吸練習支援兒童專注力發展之行動研究 =: An Action Research on using mindfulness breathing exercise to support the development of children's concentration - 王嘉蘭 (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Macau Secondary School Teachers’ Attitudes Towards Inclusive Education and Concern Over It =: 澳門中學教師對融合教育的態度與憂慮之研究 - 陳瀅瀅 (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

An Action Research on Drawing Guidance as an Intervention to Improve Chinese Writing of Primary Students with Dyslexia =: 繪畫活動介入引導讀寫障礙學生提升寫作能力之行動研究 - 黃郁羚 (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A STUDY OF GREEN FINANCIAL TECHNOLOGY ACCEPTANCE IN TONGZHOU DISTRICT OF BEIJING - An, Bo Yang (University of Saint Joseph, 2023)
China’s economy has entered a critical period of structural adjustment. The developing green industries and the transforming traditional industries have increasing demand for finance, making ""green finance"" increasingly essential. While China's green finance is in the development stage, some newly developed zones serve as pilots for the launch of green financial products. An example is Tongzhou District of Beijing, which aims to expand Beijing’s space, promote the coordinated development of Beijing-Tianjin-Hebei, and explore the optimal development mode of the densely populated economic areas. This thesis aims to study consumer acceptance of green financial technology (fintech) in the case of Tongzhou District. This thesis extended the commonly applied theoretical model for the problem of study, the Energy Augmented Technology Acceptance Model (EA-TAM), to analyze the impacts of perceived usefulness, perceived ease of use, attitude toward use, intention, usage intention, environmental awareness, and green knowledge on the acceptance of green fintech in Tongzhou District. The survey collected 403 valid responses from people that had been active in Tongzhou District. The quantitative analysis is based on structural equation modeling techniques, including reliability analysis, validity analysis, standard method deviation test, and hypothesis testing. The analytical results show that all the hypothesized factors are significant. In addition, the sample is divided into different gender groups and education groups, so that the impacts of the socio-demographic characteristics can be explored. Males’ environmental awareness and green knowledge are insignificant in determining their acceptance of green fintech. The low-educated group’s acceptance of green fintech does not significantly depend on environmental awareness and perceived usefulness
Keywords: Fintech; Green Gintech; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The Message Hidden Behind in "SQUID GAME" research on the Level of Reception between the Message conveyed by the Drama and the Audience in Southeast Asia - Angela, Choi Nga Ieng (University of Saint Joseph, 2023)

THE RELATIONSHIP BETWEEN INTERNALISING PROBLEMS, ACADEMIC ACHIEVEMENT, SCHOOL ADAPTATION, AND GENDER, AS VIEWED FROM THE PERSPECTIVES OF BOTH TEACHERS AND STUDENTS - Ao, Hoi Ian (University of Saint Joseph, 2023)
The present study aimed to analyse the differences in the internalising problems (anxiety, depression, somatic complaints), assessed by different informants (teachers and students), according to the level of academic achievement and school adaptation level in secondary students. Furthermore, we examine the gender difference in the level of internalising symptoms. Finally, we analyzed the differences between teacher-rated and adolescents' self-reported internalising symptoms. The Achenbach System of Empirically Based Assessment (ASEBA) was used for collecting informants’ data. The sample consisted of 882 secondary students (349 males and 473 females), while 50 came from public schools and 772 from private schools. No significant differences are found in internalising problems according to the level of academic achievement from both teachers’ and students’ perspectives. Generally, students who are well-adapted to the school context have the least symptoms of internalising problems compared to average and less-adapted groups from the teachers' perspective. In addition, from students’ perspectives, adolescent females present more internalising problems than males. Finally, teachers rated fewer internalising problems when compared to the students. In conclusion, the low level of awareness of teachers towards the internalising problems of students arouse attention. It is suggested that teachers should attend professional development programs in order to address to students’ internalising problems
Keywords: Internalising problems; Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph; academic achievement; gender differences; school adaptation

The 50 Reasons for Voluntary Turnover: A Qualitative Exploration of Factors Contributing to Former Teacher Attrition in Macau - Ao, I. Leng (University of Saint Joseph, 2023)
Teacher turnover is a global issue that has not received much research attention in Macau despite studies indicating that teachers in the region experience high levels of stress and burnout. Given that private school teachers account for a significant proportion (88.6%) of the non-tertiary education system in Macau, this qualitative study focused on this specific group who voluntarily resigned from their positions. Through in-depth interviews with 13 former teachers from different kindergartens, primary, and secondary schools, the research identified 50 reasons categorized into 15 factors under three categories. Although schoolrelated factors account for the most, personal reasons were found to be the primary driver. The findings of the study highlight the complex nature of teacher turnover which can be attributed to both single and multiple factors, in both direct and indirect forms. The factors could also interplay in both unidirectional and mutual relationships. A conceptual framework for teacher turnover in Macau was developed to address the 15 contributing factors and the complex interplay of these factors. This study could fill the gap in the literature and serve as a valuable resource for policymakers and school leaders seeking to reduce teacher attrition rates in the region
Keywords: Macau; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph; leavers; teacher turnover

Plugin Program Reconfigurable Architecture System For Sustainable Future - Au Yeung, Kam Sheung (University of Saint Joseph, 2023)
The primary research focus of this dissertation revolves around the concept of a "plugin" program. It raises a fundamental question about whether a building can attain long-term usability through metabolic flexibility (plugin units and their reconfigurable space), promoting adaptability (accommodating various program transfers), and meeting sustainable future criteria. Specifically, this dissertation inquires whether this "plugin" building design, with its reconfigurable units and metabolic system, can adapt to different spatial programs and become sustainable architecture
Keywords: Building program transfer; Metabolism Architecture; Plugin capsule units; Reconfigurable; Sustainable Architecture; Theses and Dissertations Master of Architecture (MARCH); University of Saint Joseph

How digital technology changes our way to interact with others at the workplace in Macau - Pre and post-pandemic - Austin, Lei Iat Pong (University of Saint Joseph, 2023)

"The Never-Ending Task": A case study on Performing Arts with People with Intellectual Disabilities in Macau - Carol, Wong Weng Si (University of Saint Joseph, 2023)

澳門私立融合教育學校中資源教師現況與問題之研究 =: A RESEARCH STUDY ON THE CURRENT SITUATION AND FACING PROBLEMS OF RESOURCE TEACHERS IN PRIVATE INCLUSIVE EDUCATION SCHOOLS IN MACAO - Chan, Lok In (University of Saint Joseph, 2023)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 澳門; 私立融合教育學校; 融合教育; 資源教師

The attractiveness of Taobao: why do people always come back despite negative feedback - Chan, Nga Man (University of Saint Joseph, 2023)
Online shopping in Macau has developed rapidly in recent years. And the success of Taobao is significantly hard to not notice. Its’ sales are breaking the record every year. However, there are a lot of negative comments towards Taobao. Various researches and data have shown that live-streaming is one of the biggest contributions towards Taobao’s sales and record breaking. This research aims to investigate deeply to understand how Taobao counters those issues and the role of live-streaming in relation to it. Based on a review of the literature in the relevant areas , qualitative methodology is adopted after thorough considerations. A small sample size of 10 were selected to conduct semi-structured in-depth interviews and the participants agreed to respond to answer the original interview questions and the follow-up questions. Analysis of the responses demonstrated e-customer service is the most influential variable towards repurchase intention. Live-streaming strategy can effectively and directly reduce constomer’s uncertainty of products and increase the efficiency of responsiveness. And product uncertainty and responsiveness speed are variables that impact purchase intention. The result demonstrated live-streaming's effectiveness in combating multiple negative aspects of Taobao and strengthening the positive aspects. On this basis, live-streaming is an impactful method to combat Taobao. In addition, e-service in terms of sufficiency of the staff’s communication skill have been found important towards customer’s satisfaction. A gap related to such an issue has been recommended in the further research recommendations along with other factors or sample groups, which are needed to explore deeply in the future
Keywords: Authenticity; Customer satisfaction; E- Service quality; Repurchase intention; Taobao; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

THE RELATIONSHIP BETWEEN PSYCHOPATHOLOGY AND RESILIENCE OF SECONDARY SCHOOL STUDENTS IN MACAO - Chan, Ngan Ieng (University of Saint Joseph, 2023)
School-age children and adolescents face several psychological conditions frequently associated with negative consequences on behavioral and mental problems. Their level of mental resilience may affect their responses to academic or interpersonal issues and coping with challenges, which in turn affects their mental health. This study aims to characterize the current status of the psychopathology and resilience of secondary students and to analyze the relationship between psychopathology and resilience in a sample of 80 girls aged 12–18 was selected by cluster sampling from one private secondary school with six grades in Macao. In this study, we used the Achenbach System of Empirically Based Assessment (ASEBA) to assess behavioral and emotional problems and the Resilience Scale for Chinese Adolescents to assess resilience. A total of 78 valid questionnaires were obtained for CBCL, 78 for TRF, 80 for YSR, and 77 for Resilience Scale and data were analyzed by using SPSS. The results reveal that clinical prevalence of Total Problems (YSR, 27.5% > CBCL, 19.2% > TRF, 15.4%) and Internalizing Problems (YSR, 22.5% > CBCL, 17.9% > TRF, 11.5%) from the perspective of adolescents was higher than that from the perspectives of parents and teachers. Senior students exhibited higher frequency on the borderline clinical range than Junior students. (χ2(2, N=80) =14.56, p<.001). The average score of resilience is 3.24±0.51, which is above the middle level. Regarding the YSR scale and Resilience scale, we found that the score of Affect Control is significantly negatively correlated with the score of Internalizing Problems (r = -.354, p<.01). Family Support is also significantly negatively correlated with the score of Internalizing Problems (r = -.302, p<.01). Good affect control and family support can reduce various emotional and behavioral problems. The results of the study found the resilience level can negatively affect internalizing problem behaviors and externalizing problem behaviors. The results are promising and can give clues for preventing and promoting measures regarding mental health issues to both family and school education contexts, as creating a sustainable development strategy of improving adolescents’ mental resilience quality
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph; psychopathology; resilience; secondary students

METAVERSE: A STUDY OF CONSUMER PERSPETIVE IN MACAU - Chan, Vanda Cardoso (University of Saint Joseph, 2023)
Technology is an essential and valuable tool nowadays. New technology and innovations are introduced to the public day by day. Metaverse will be a new trend, as the Macau government has been trying to promote this technology since the COVID-19 pandemic is still here. Before this technology goes deeply to the public, this paper attempts to examine the consumer’s perspective of Metaverse and understand the cognition of Macau people about Metaverse. And bring out what factors and conditions will make them accept this technology. A qualitative research method will address the questions and problem to understand consumer perspectives towards this technology. Entrepreneurs, managers, and professionals will be invited to take part in this research. Ten interviews will be carried out in this research for data analysis, which may provide a board overview of this technology in Macau and give recommendations to local entrepreneurs. In conclusion, consumers think it is still not a well-developed technology and is not globally used at this stage. In contrast, if this technology is ready-to-use, it will be a helpful assistant in their businesses. They expect the metaverse to be fully developed in ten or more years
Keywords: Consumer perspective; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph; augmented reality; extended reality; marketing strategy; virtual reality

INDOOR AIR QUALITY (IAQ) MANAGEMENT IN MACAO: MONITORING PARTICULATE MATTER (PM10 AND PM2.5) AT THE RENOVATION SITE IN LARGE SHOPPING MALLS - Chan, Weng Ian (University of Saint Joseph, 2023)
"Over time, the large shopping malls in Macao will require some changes to improve space utilization, resulting in renovation projects that affect indoor particulate matter (PM10 and PM2.5) concentrations. Employees work long hours in an environment where the ambient air quality is poor, directly affecting their work efficiency. Nonetheless, the concentration of PM produced by the interior renovation of shopping malls has yet to receive particular attention. Therefore, this study will investigate IAQ, in particular, PM10 and PM2.5 in large-scale shopping mall renovation projects in three different indoor locations (i.e., public, renovation, and construction areas) to understand the causes of indoor PM10 and PM2.5. This study will collect on-site PM data for analysis, examine whether the current control measures are appropriate and propose some improvements. The data collected will be compared with IAQ standards from the World Health Organization (WHO) and the Macao Meteorological and Geophysical Bureau (SMG), specifically PM concentrations. The research results can provide a reference guide for decision-makers, management, construction teams, design consultant teams and renovation teams of large-scale projects. In addition, the monitoring of IAQ can ensure a comfortable environment for employees and customers."
Keywords: Construction Dust; Health Exposure; PM Monitoring; Particulate Matter; Thesis and Dissertations Master of Environmental Sciences and Management (MESM); University of Saint Joseph

Gender Differentiated Parenting and Family Characteristics Affecting Parent-Adolescent Relationship in Macao: Che Iok Seng a.k.a Matthew - Che, Iok Seng (University of Saint Joseph, 2023)
This study aims to investigate gender-differentiated parenting and the factors that affect parent-adolescent relationships in Macao families. The study will address the following research questions: A) Does gender-differentiated parenting exist in Macao families? B) How does the academic level of parents relate to conflict resolution and acceptance levels? C) How does the length of time parents have lived together relate to conflict resolution and acceptance levels? D) How does the sibling position of adolescents relate to conflict resolution and acceptance levels? The study employed a quantitative research approach with a purposive and convenient sample of parents with children aged between 12 to 18 years old in Macao. The data were collected using the Parent-Child Interaction Questionnaire—Revised-Parent version (PACHIQ-R-P) through a questionnaire survey from May to August 2022. Out of the 172 completed questionnaires, seven were invalid, resulting in 165 valid questionnaires. The findings showed that gender differentiation in parenting was confirmed, with significant results showing that fathers had lower acceptance and conflict resolution levels when their child was a boy. Mothers showed similar acceptance and conflict resolution levels regardless of their child's gender. Furthermore, the study found that parents' acceptance of their children was influenced by their academic level, length of time living together, and the child's sibling position. This study is the first of its kind in Macao and could provide valuable insights for family and adolescent services in the region
Keywords: Adolescents; Conflict Resolution; Gender differences; Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

ONLINE IMPULSE BUYING BEHAVIOR: A STUDY OF MACAU CONSUMERS - Cheong, I. Lam (University of Saint Joseph, 2023)
Due to the expansion of the Internet and advancements in technology, e-commerce has been frequently and widely used nowadays. The popularity of online shopping continues to develop and become increasingly common, yet, the concept of impulsive buying has consistently drawn significant attention over the years. In order to fit into the current shopping trend, recognizing the needs and wants of online shoppers as well as providing appropriate approaches are essential tasks for companies to achieve. The question of how to attract consumers to make purchases has been a concern for a long time, and in fact, it is necessary to explore consumers’ online purchase decisions in relation to their impulse buying behavior. In accordance with current academic knowledge, the main objective of this study is to investigate factors that influence consumers' online impulsive buying behavior based on external stimuli (such as sales promotions and websites characteristics) and the elements of marketing mix strategy (product, price, place, and promotion). According to the analysis, the promotion strategy has been identified as the most significant influence on consumers’ decision to make an online impulsive purchase. Therefore, the findings from this study are beneficial for companies and marketers to build a framework in order to develop suitable and effective strategies in order to encourage and stimulate consumers' desire for purchases. Furthermore, the research applies the qualitative methodology by conducting semi-structured interviews with 11 consumers who have previously experienced an online impulse buying
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph; e-commerce; external stimuli; marketing mix strategy; online impulse buying; online shopping

COMMUNICARE - an Interactive Multisensory Application to Care for Trees in Macao - CHEONG, WENG IAN (University of Saint Joseph, 2023)

Challenges and Possibilities of Cultural Heritage: The Case of Portuguese Tiles (Azulejos) in Macau - Chu, Hou Man (University of Saint Joseph, 2023)
Macao is a city of culture, and history and culture are the wealth of Macao. Over the centuries, the exchange and transmutation of Chinese and Western cultures have given Macao a unique cultural charm, and have also formed and preserved a considerable amount of cultural heritage. Cultural heritage has received increasing attention from all sectors of the community in the tourism industry in Macao, the promotion of the preservation and transmission of cultural heritage through tourism development has become a new issue in the tourism sector. As an independent art form in the urban public space, tile painting has both practical and aesthetic functions, and is a special vehicle for the convergence of multiple cultures in the urban cultural ecology. It is also a medium through which the city's cultural message can be fully disseminated. The paper presents a detailed analysis of the strengths, weaknesses, opportunities and challenges of the development of Macao's cultural heritage tile murals, based on an introduction to the existing status of Macao's cultural heritage tile murals, using the SWOT analysis method, which provides a reference for Macao's cultural heritage tourism
Keywords: Azulejo; Cultural heritage; Macao; SWOT analysis; Strategy; Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph

Comparative study: The Human rights situation in China, the USA and Europe - Chu, Pok Tou; Lao-Phillips, Jenny Oliveros (University of Saint Joseph, 2023)
This thesis mainly discusses and compares the human rights situation and the problems in China, the USA and the UK. Also, the thesis will give the solution of how to make the world's human rights situation more fairly. Because we sometimes listen to these countries use cruel ways to suppress the opponents from the news. So I think this will be very suitable for understanding the current human rights situation, problems and movements in these countries. This thesis mainly uses the secondary data analysis method to collect and analyse the data. After analysing the data, three main issues affecting human rights were identified. These issues are race, religion, and network privacy. Other important factors still influence human rights, but this dissertation focused on the three issues identified. Finally, I will give two to three recommendations to practice human rights more fairly. Although the step will be very small, we can greatly improve the fair human rights in the future
Keywords: China; Europe; Human rights; Human rights situation; Thesis and Dissertations Master of Government Studies (MGS); USA; United Kingdom; University of Saint Joseph

CHARACTERIZARION OF ENVIRONMENTAL NOISE IN MACAO S.A.R. OVER THE PAST DECADE: IMPLICATIONS FOR NOISE POLLUTION MANAGEMENT - Deng, Ziyang (University of Saint Joseph, 2023)
With the rapid urban development, Macao SAR has become one of regions with the with highest population density in the world, characterized by high traffic flow and dense building aggregations. Noise has become one of the major environmental problems in Macao. Besides having an impact on human health and wellbeing, noise pollution is known to impact ecological systems and the image of a place. Before proposing a plan to reduce noise pollution, it is necessary to have a general understanding of the current noise levels in Macao, how they have changed over time and the main noise pollution sources and environmental concerns. This dissertation relies on the publicly available data from DSPA (Macao Environmental Protection Bureau) monitoring stations concerning noise levels over the past decade. The main research goals were: 1) Characterize changes in noise levels from 2010 to 2021 during daytime, nighttime, and full-day from multiple noise stations located in Macao, Taipa, and Coloane Peninsula; and 2) associate changes in noise levels with potential factors such as location, number of residents/tourists, number of vehicles, among others. This work provides an important framework for future studies concerning noise monitoring and mitigation strategies
Keywords: Environmental policies; Legislation; Master of Environmental Sciences and Management (MESM); Noise management; Noise pollution; University of Saint Joseph; mitigation

TO EXPLORE SMOKING BEHAVIORS OF ADULTS IN MACAO: DISCOVERIES BY QUANTITATIVE AND QUALITATIVE STUDIES - Dias, Luis Borges (University of Saint Joseph, 2023)
The purpose of the study was to explore the smoking behaviour of the smokers living in Macao. I was part of the 1st group of doctors to have chosen to initiate smoking cessation in Macau. In addition to my diverse academic background of study in laws- a dissertation about the effect of tobacco control program in Macao (submitted in 2011), a master in Public Administration, and five years of working experiences as an Inspector Assistant of tobacco, I had the conviction that I have to write to share my experience and knowledge about smoking cessation to contribute to the field of counselling and psychotherapy as there is little research data concerning smoking prevalence and demographics in Macao. This study consists of two parts – PART I presents the quantitative data collected by a questionnaire-survey over 1378 smokers and PART II qualitative data from semi-structured interviews with 10 adult smokers to explore their experiences of smoking and smoking cessation in Macao. Quantitative data analysis was conducted with the SPSS, while qualitative analysis with coding and theme identification by following the grounded theory procedures. The study found that about 85% smoker surveyed consumed more than half a pack of cigarette per day and about 31% reported various symptoms like irritability, fatigue, loss of appetite and difficulties in concentration. The qualitative study has identified major positive factors related to initiation and maintenance of smoking cessation, namely health concerns, financial concerns and family support. Major negative factors related to relapse of smoking are peer influences, smoking of family members, and impacts of stressful life events. Based on findings of the study, it is argued that preventive anti-smoking education should be implemented among young people. Promotion of health education and preventive anti-smoking strategist and policy in Macao are discussed. The data collected indicate the fact that individuals who have pathologies of the cardiovascular system as a motivating factor for contemplating or taking actions for smoking cessation. Moreover, financial problems, gender (male predominantly), married with family support, higher educational level, without psychological diseases, better economic status, lower nicotine dependent are predictors to success in quit smoking. It also raises the possible need to deepen some evaluation parameters hither to be only superficially addressed. Therefore, and by limitations inherent to the study, this hypothesis needs further investigation. I argue that non-pharmacological treatment methods alone have proven to be effective in the smoking cessation process. However, it is argued that this combined with pharmacological therapy, in particular in specialized consultations, would be more effective and capable in increasing success rates in smoking cessation
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph; grounded theory; relapse; smoking behaviour; smoking cessation

EVALUATING SATISFACTION OF LOCAL ROAD USERS OF MACAU - Fong, Chi Cheng; Pinheiro, Francisco Vizeu; Lei, Weng Chi (University of Saint Joseph, 2023)
"Macau's rapid economic development in recent decades and relatively low usage of public transportation have put considerable pressure on the city's carrying capacity. Improving the transportation system has been a major policy goal of Macau's urban planners. To deepen the understanding of the perspectives of local road users, this dissertation's main research question is: what factors determine the satisfaction of local road users of Macau? After collecting responses using an online questionnaire, quantitative research methods were adopted to analyze travel patterns, satisfaction toward different road usage dimensions, and sociodemographic characteristics of local residents. 145 responses were collected and quota samples were generated to match the distribution of each sociodemographic feature of the population. Most respondents used private vehicles to travel during peak hours on weekdays for work or for school and to travel during the entire afternoon and evening on weekends for shopping necessities and for leisure. The most traveled districts were Baixa de Taipa, Costa & Ouvidor Arriaga, and Baixa de Macau. It was found that the mean overall satisfaction score inclined to the dissatisfaction side (below 3). Only clarity of traffic lights and number of road signs (measuring infrastructure) and temperature and price of fares (measuring public transportation) had mean satisfaction scores that were significantly higher than 3, indicating higher satisfactions. Meaningful hypotheses regarding the differences of different road user groups were set out, then Kruskal-Wallis ANOVA tests and Mann-Whitney U tests were run. The significant findings were such that the elderly aged 65 or above were less satisfied and the unemployed were more satisfied with road usage. The better educated were more satisfied with the environment, and the unemployed were more satisfied with the public transportation. Drivers were less satisfied with transportation costs, and peakhour road users were less satisfied with the infrastructure. The Spearman correlation analyses found that infrastructure had moderately positive correlation with facilities and with travel safety. Based on the findings and their policy implications, policy suggestions could be made. The policies suggested in this study should have favorable short-term and long-term effects on more than one road usage aspects."
Keywords: Public transport; Survey questionnaire; Thesis and Dissertations Master of Government Studies (MGS); Traffic congestion; Transportation; Transportation services; University of Saint Joseph

THE POWER OF SCENT MARKETING: INFLUENCING CONSUMERS TO PURCHASE - Fong, Un I. (University of Saint Joseph, 2023)
Examining consumer perceptions of scent marketing in Macau's retail setting is the goal of this study. The study focuses on the following two primary uses of scent marketing in retail environments: subliminal application and application as a component of branding strategy. Qualitative research methodology is used. A total of ten consumer interviews produced the data. The findings show that consumers are in favor of scent marketing's use in retail settings. The use of scent marketing as a tool for establishing brands is preferred, and consumers find this approach to scent marketing to be more acceptable than its subliminal application. Although consumers believe that other factors, such as price, are typically more significant than scent when making purchases, the use of subliminal scents was not always evaluated negatively. Unless occasionally when making an unplanned purchase, consumers do not think that a subliminal scent can significantly impact their purchasing behavior
Keywords: Consumer behavior; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph; branding; consumer opinion; marketing strategy; scent marketing; subliminal advertising

Effective Promotion for Old Tea Restaurant Base On Marketing Mix Approach After Covid-19 Pandemic In Macau - Ho, Ka Ian (University of Saint Joseph, 2023)
This research paper analyses the marketing efforts and important attributes of Macau tea restaurants that have been open for more than 20 years, especially the digital methods that tea restaurants have used to sustain their business and meet customers' needs in the era of digital transition after the onset of the 2019 Covid 19 pandemic year. Using online marketing channels nowadays become an important tool for communicating with customers today. Despite the old Tea Restaurants in Macau did not put much efforts on digital channels for communication yet, to find out how tea restaurants survive in the rival restaurant industry in Macau, qualitative and quantitative methods were used to see how they meet the needs of their customers. For the quantitative method, an online survey questionnaire in bilingual English and Traditional Chinese was conducted with 280 respondents on customer purchase habits, importance of restaurants’ attributes and social media insights on tea restaurants, and the data was analysis by SPSS for the relationship and significance. For the qualitative method, 7 interviews were conducted with the business owners of the old tea restaurants which that have been opened for more than 20 years, including marketing efforts and their attitudes towards digitalization. To find out the marketing strategy of Macau’s old tea restaurants in the digital transformation era, it was found that “place” and “product” are the most important marketing mix for customers. Tea restaurant owners focus on product quality, and generate “word-of-mouth” which is customer-generated marketing, and is an effective way to influence customers for local tea restaurants. Meanwhile business owners will consider digitalize in the near future as well to match the new young customers’ online habits and the need for “place” such as online delivery platform
Keywords: Macau; Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph; digitalization; marketing mix; tea restaurant

HOW DO FOOD INFLUENCERS ON INSTAGRAM AFFECT CONSUMERS’ VISIT INTENTION TO RESTAURANTS IN MACAU? - Ho, Pui I. (University of Saint Joseph, 2023)
This dissertation examines consumers' perceptions of food influencer content on Instagram and the relationship between exposure to food influencer reviews and consumers' intention to visit restaurants in Macau. A mixed-method research design was employed, combining quantitative survey data from 301 responses with qualitative insights from one focus group session involving six participants. The findings suggest that consumers find food influencer content entertaining and inspiring for dining out and exploring new culinary experiences, but they express concerns over its credibility. While food influencer content has a good exposure to consumers, it has a moderate impact on consumers’ restaurant choices, with various factors affecting the relationship. The results highlight the importance of perceived trustworthiness and enjoyability of food influencer content, the visual appeal of food and restaurant environments in photos, and personal relationships in shaping Macau consumers' visit intention to restaurants. The findings can serve as a basis for future research on credibility perceptions of food influencers, the enjoyability of influencer content, and the visual appeal of food and restaurant environments on Instagram. Practically, food influencers should prioritize transparency, authenticity, appealing photos, engaging captions, and leverage the role of personal relationships to increase their impact on consumers' restaurant choices
Keywords: Instagram; Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph; food influencers; influencer marketing; social media

Food Waste Management In Macau: Assessing Public Awareness, Recycling Facilities, And Policy Implementations In Comparative Perspective - Hoi, Hang Ian (University of Saint Joseph, 2023)
Food waste has become an increasingly pressing issue worldwide, and Macau is no exception. A substantial portion of municipal solid waste in Macau is comprised of organic waste, with household food waste being a significant contributor. This can be attributed to households purchasing excessive food, preparing more than necessary, or not consuming items before they spoil, leading to detrimental resource and environmental impacts, particularly in the form of greenhouse gas emissions. It is crucial for Macau to develop a sustainable food waste management system that fosters prevention and responsible consumption and to develop food waste recycling habits among its residents. This study employed a two-pronged approach: a literature review of food waste source separation policies and practices in four neighboring regions to identify adaptable good practice examples for Macau, and a questionnaire survey completed by 143 local residents. The survey aimed to comprehend residents' behaviors and awareness regarding food waste prevention and treatment, evaluate their satisfaction with Macau's existing food waste recycling program, examine their resistance and motivation toward participating in the recycling program, and assess their attitudes toward implementing a polluter-pays-principle system in Macau. The survey aimed to provide insights into the current state of household food waste in Macau and inform future waste management policies and strategies of stakeholders. The survey findings highlight the need for enhanced public awareness and education on food waste prevention. Additionally, upgrading recycling facilities may encourage residents to participate more actively in food waste recycling. Ultimately, implementing suitable policies can help prevent food loss and waste and regulate food waste generation and elevate recycling rates. This study offers preliminary recommendations for policymakers or government entities as a orientation for future planning
Keywords: Food Loss and Waste (FLW); Food Waste Hierarchy; Food Waste Management; Food Waste Separation; Sustainable Development Goals (SDGs); Thesis and Dissertations Master of Environmental Sciences and Management (MESM); University of Saint Joseph

VALUE-BASED ADOPTION OF MOLECULAR CHINESE MEDICINE (MCM): AN EXPLORATORY INVESTIGATION - Hong, Chi Kit (University of Saint Joseph, 2023)
The world we live in today is constantly changing, with new technologies and innovations being introduced all the time. Through the continuation and innovation of Chinese medicine theories, scientific research methods, and progress, Traditional Chinese Medicine continues to evolve and develop more innovative Modern Chinese Medicine. In this research, Molecular Chinese Medicine is studied as a new form of Chinese medicine, intended to provide a more pleasant and safe experience for consumers. Thus, the objective of this study is to identify both positive and negative perceptions that contribute to the adoption of innovative technologies and their related products. In order to reach this goal, a robust value-based theoretical model is used. To examine behavioural intentions to adopt Molecular Chinese Medicine (MCM) in Macau, this study combines quantitative and qualitative methods. Thus, a Value-based Acceptance Model (VAM) was used to determine Macau citizens' attitudes towards Molecular Chinese Medicine, including their perceptions of its usefulness, enjoyment, technicality, and perceived fee, in relation to the perceived value of the product, which may ultimately determine adoption intentions. Structural Equation Modeling (SEM) was used to process a sample of 194 Macau residents. The data analysis supported our model's explanatory and predictive power and helped describe the characteristics of the local population. Our results provide insight into the acceptance of innovative products that may be useful in designing more accurate strategies and facilitating the introduction of MCM to Macau and similar markets. It was found that low perceived fees demonstrated a relatively strong positive correlation with potential users' perceived value, whereas usefulness and enjoyment showed a medium-strong positive correlation. Also, a strong positive correlation was found between potential consumers' perception of the value of Molecular Chinese Medicine and their intention to adopt it
Keywords: Molecular Traditional Medicine (MCM); SmartPLS; Technology Adoption; Thesis and Dissertations Master of Business Administration (MBA); Traditional Chinese Medicine (TCM); University of Saint Joseph; Value-based Adoption Model (VAM)

NEUROFINANCE - ANALYZING AND UNDERSTANDING STOCK TRADER’S DECISION-MAKING PROCESS BASED ON REAL-TIME MONITORING OF EMOTIONAL REACTIONS - Hsu, Hsin-Tzu (University of Saint Joseph, 2023)
Human emotions can be meticulously associated with decision-making, and emotion can generate behaviours. Due to the fact that it could be bias and exhaustively complex to examine how human beings make choices, important groups of study in finance are stock traders and non-traders. The objective of this work is to analyze the connection between emotions and the decision-making process of investors and non-investors to understand how emotional arousal might dictate the process of deciding policy. As facial expressions are fleeting, neuroscience tools such as AFFDEX (Real-Time Facial Expression Analysis), Eye-Tracking, and GSR (galvanic skin response) were adopted to facilitate the experiment and its accompanying analysis process. Thirty-seven participants attended the study, ranging from 18 to 72 years old; the distribution of investors and non-investors was twenty-four and thirteen, respectively. The experiment initially disclosed a thought-provoking result between the two groups under the certainty and risk-seeking prospect theory; there were more risk-takers among non-investors at 75%, while investors were inclined toward certainty at 79.17%. The implication could be that the non-investing individuals were less complex in thought and therefore pursued higher returns besides a high probability of losing the game. In addition, the automatic emotion classification system indicates that when non-investors confronted a stock trending chart beyond their acquaintance or knowledge, they were psychologically exposed to fear, anger, sadness, and surprise. Investors, on the contrary, were detected with disgust, joy, contempt, engagement, sadness, and surprise, where sadness and surprise overlapped in both parties. Under time pressure conditions, 54.05% of investors or non-investors tend to make decisions after the peak(s) of emotional arousal. Variations were found in the deciding points of the slopes: 2.70% were decided right after the peak(s), 37.84% waited until the emotions turned stable, and 13.51% were determined as the emotional indicators started to slide downwards. Several combinations of emotional responses were associated with decisions. For example, negative emotions could induce passive decision-making, in this case, to sell the stock; nevertheless, it was also examined that as the slope slipped downwards to a particular horizontal point, the individuals became more optimistic and selected the "BUY" option. The support of physiological monitoring tools makes it possible to capture the individuals' responses and discover the science of decision-making. Future works may consider expanding the study to more significant demographic populations for further discoveries
Keywords: Decision-making; Emotions; Investors; Physiological Monitoring; Stock Trading; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Primary teachers' burnout at the inclusive education schools in Macao - Ieong, Iek Kuan (University of Saint Joseph, 2023)
"In 2021/2022 academic year, there are 2,244 SEN students in Macau and its growth rate is 36% in ten years. However, at the present, there are 38 schools providing the related education to them. Admittedly, this is an unbalanced supply and demand. In fact, the teachers who work at inclusive education schools are bearing all responsibility to teach SEN students and their mental health is worth to attention. Moreover, there are 1,224 SEN students in primary (2021/2022 academic year), it accounting for 55% of all. That is, the numbers of their teachers are the most and they are representative. Therefore, exploring primary teachers’ burnout at inclusive education schools becomes the topic of this study, even more important, it is including to compare normal and resource teachers. This topic is rarer currently in Macau. On the one hand, emotional exhaustion, depersonalization and (reduced) personal accomplishment are dimensions of burnout (Maslach et al., 1996). These become the dependent variables of this study. According Ecological Systems Theory (Bronfenbrenner, 1979) and the factors of self-efficacy in inclusive education (Sharma et al., 2012), the following hypotheses are provided to guide this study: (1) normal teachers’ emotional exhaustion, depersonalization and reduced personal accomplishment are higher than those in resource teachers; (2) teachers’ attitudes into inclusive education, (3) teachers’ self-efficacy to use inclusive instruction (SEII), (4) teachers’ self-efficacy in collaboration (SEC) and (5) teachers’ self-efficacy in v managing behavior (SEMB) both are negatively related to emotional exhaustion, depersonalization and reduced personal accomplishment; (6) teachers’ stress of Covid19 is positively related to emotional exhaustion, depersonalization and reduced personal accomplishment. On the other hand, quantitative methodology, and snowball sampling are used in this research. At last, 132 responds are collected, including 100 normal teachers and 32 resource teachers. They are from 48 inclusive education schools in Macau. All data were analyzed by SPSS 25.0. The results of this study are followed: (1) teachers’ emotional exhaustion level is middle, their depersonalization and reduced personal accomplishment levels both are low; (2) resource teachers’ emotional exhaustion and depersonalization are higher than normal teachers; (3) teachers’ attitudes into inclusive education negatively related to depersonalization but positively related to reduced personal accomplishment; (4) in the factors of self-efficacy, only SEII is negatively related to reduced personal accomplishment; (5) teachers’ stress of Covid-19 is positively related to emotional exhaustion, depersonalization and reduced personal accomplishment."
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

澳門家校合作中的親師溝通: 以某小學為例 =A STUDY ON PARENT-TEACHER COMMUNICATION IN HOME-SCHOOL COOPERATION IN A PRIMARY SCHOOL IN MACAU - Io, In Chi (University of Saint Joseph, 2023)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 家校合作; 小學; 澳門; 親師溝通

Exploring Features and Behaviors of 'GUNDAM MOBILE SUIT' Enthusiasts in China 's Online Digital Society - Joel, Chao Chou U (University of Saint Joseph, 2023)

ORGANIZATIONAL JUSTICE AND PSYCHOLOGICAL WELL-BEING AMONG HEALTHCARE WORKERS IN MACAO - Kaewmanee, Celina dos Santos (University of Saint Joseph, 2023)
This study examined the relationships between organizational justice, job satisfaction, and subjective well-being of medical doctors and nurses in Macao. It applied a quantitative methodology through a cross-sectional applying self-response questionnaires to 149 healthcare workers. Consistent with the group-engagement model (Tyler & Blader, 2003), findings indicate that organisational justice and job satisfaction improve subjective well-being. Yet, inconsistent with the model and our hypotheses, organizational justice did not affect work satisfaction. Finally, nurses experienced less positive justice perceptions than doctors. The study provides insights into the relationship between organizational justice, job satisfaction, and subjective well-being among healthcare professionals, which might help enhance working conditions. Healthcare organizations should prioritize promoting job satisfaction and justice perceptions to increase healthcare personnel's subjective well-being. The cross-sectional design limits causal inferences about variable relationships, and the self-reported data may have social desirability or response biases. Still, the originality and value of this paper lie in its contribution to the literature on the well-being of healthcare workers, particularly in the unique context of Macao. To our knowledge, this is the first study in Macao to examine the relationship between organizational justice, job satisfaction, and subjective well-being among healthcare workers
Keywords: Healthcare; Job Satisfaction; Organizational Justice; Subjective well-being; Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph

澳門融合教育下資源老師心路歷程之質性研究 =: A QUALITATIVE STUDY ON THE SPIRITUAL JOURNEY OF RESOURCE TEACHERS IN INCLUSIVE EDUCATION IN MACAO - Ke, Li Ping (University of Saint Joseph, 2023)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 心路歷程; 融合教育; 資源老師; 質性研究

THE MODERATING EFFECTS OF POWER DISTANCE ON THE RELATIONSHIP BETWEEN PERCEPTIONS OF ORGANISATIONAL POLITICS AND ORGANISATIONAL JUSTICE - Kong, Fion Ming Ying (University of Saint Joseph, 2023)
The aim of this research is to investigate how power distance orientation effects the relationship between perceptions of organisational politics and perceptions of organisational justice. A quantitative cross-sectional study was conducted on 172 full time workers in Macau, where respondents self-responded to questionnaires that were translated back-to-back into Chinese in order to accommodate the populations native language. This study found that power distance was contrary to our initial hypothesis of high-power distance equals to high politics and low justice. It was found that high power distance in facts equates to lower political perceptions and higher justice perceptions. This study contributes to understanding power distance in Macau as it is not noted in the Hofstede cultural dimensions. We also learned that having a longer distance between a position of power can contribute to less political activity and more sense of justice for the employees
Keywords: Organisational Justice; Organisational Politics; Power Distance; Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph

Externalizing Behaviour in Macao: Gender and Parental Participation - Kuok, Oi Lou (University of Saint Joseph, 2023)
There are gaps in the research on gender differences and parental participation and the interaction between gender and parental participation in non-Western cultural contexts, particularly the Macao context. The current study aims to fill these gaps by examining gender and parental participation (i.e., father only, mother only, or both) differences and interactions in externalizing behaviour (oppositional defiant disorder and conduct disorder) during late childhood and adolescence (i.e., from age 10 to 18) in Macao. The methodological approach for the current study was a cross-sectional design with a quantitative methodology based on self-rated questionnaires. In certain items, we did discover gender differences. More boys than girls appeared to concur that they occasionally misbehave at school or start fires. And it appeared that girls were more likely than boys to concur that they occasionally exhibit unexpected mood or emotion changes and strong tempers. The children in the groups where only the mother or father participated tended to agree more than they prefer to hang out with older kids than kids their own age. This is in contrast to the group with more parental participation, which is represented by both parents submitting the questionnaire. Although none of the hypotheses proposed were supported, our outcomes implied culture and subculture may play important roles on youths’ externalizing behaviour
Keywords: Externalizing behaviour; Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph; gender; parental participation

澳門普通班教師與資源教師合作教學現況與改進建議之個案研究 =: A CASE STUDY OF CO-TEACHING PRACTICES AND IMPROVEMENT SUGGESTIONS AMONG GENERAL EDUCATION TEACHERS AND RESOURCE TEACHERS IN MACAO - Lai, Chong Weng (University of Saint Joseph, 2023)
Keywords: Inclusive education; Resource teacher; Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 合作教學; 澳門; 融合教育; 資源教師

Exploring Macau Primary School Teachers’ Understanding and Practices of Educational Innovation - Lai, Hoi In (University of Saint Joseph, 2023)
Teaching methods are not enough in today's social environment. By studying the understanding and practice of innovative education by primary school teachers in Macao, we can find a direction to promoting educators' demand for educational innovation. This research aims to understand the attitudes of primary school teachers in Macao toward innovative education, as well as the feasibility and necessity of developing a creative curriculum, through in-depth interviews with the experiences and reactions of primary school teachers in Macao. Simultaneously, encourage primary school teachers in Macao to implement effective and innovative educational methods so that Macao society can rethink the importance of educational innovation. The significance of the research lies in improving teachers' awareness of educational innovation and promoting teachers' understanding of education. In education, innovation includes new teaching theories, methods, techniques, and resources. Therefore, the education innovation is to think about things creatively, and innovation is to do creative things. By interviewing eleven local primary school teachers in Macau, we learned their views on innovative education teaching methods. Although, a limitation of the study is that only a few faculty members were selected, which may not represent the entire primary teacher in Macau. The study draws four main conclusions, the first of which is the view of primary teacher in local education, it can know that Macao primary school teachers understanding and cognition of educational innovation. Though of understanding of Macau’s primary teacher’s attitude in innovation teaching, which can find the feasibility of innovation teaching in Macau. At the same time, understanding of the impact factor in Macau innovation education, it clarifies the main challenging of primary teacher practice innovation teaching in Macau. On the other hand, thought of understanding of teacher’s attitude, we can more understanding the real situation in Macau’s educational innovation and encourage the teacher promoted educational innovation in Macau
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Perception on occupational stress in the Hospitality Industry in Macau - Lam Chi Ieng (University of Saint Joseph, 2023)
Employees in the hospitality industry, in particular, face difficult conditions such as overwork, job security, understaffing, and work-life imbalance in today's fast-paced society. Because of that, employees in the hospitality industry experience high levels of occupational stress. Severe conditions of occupational stress may not only lead to health issues for the employee but also affect their work performance. In order to get a better grasp of how occupational stress affects the employees in the hospitality industry in Macau, the research questions are: 1) What are the sources of stress in the Macau hospitality industry? 2) How does the COVID-19 pandemic change the perception of occupational stress among employees in the Macau hospitality industry? How do the companies help the employees in the Macau hospitality industry cope with occupational stress? have been formulated. Semi-structured interviews were conducted with eleven participants working in the hospitality industry, with a median age of 39 years and a median range of 13 years. Based on these interviews, participants expressed their perceptions of occupational stress under the categories of distress and eustress, while coding schemes were applied to all semi-structured interviews. The results on distress showed that reactions from employees and their working conditions, in particular, were the two most important determinants of occupational stress, while motivation helped people grow and develop their confidence. For the changes in occupational stress due to the pandemic, mental reactions from employees were the most significant determinant of occupational stress in the Macau hospitality industry during the changes brought about by the pandemic in these years, closely followed by employee job insecurity. In order to cope with occupational stress, employees should take responsibility for coping with their stress, but employers also have a role to play in this process, like providing good communications and proactive assistance to the employees. Finally, employees' responses were described as more negative as a result of their experience. Further research could focus on more methods for employees to cope with occupational stress in both physical and mental ways
Keywords: Stress; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph; hospitality industry; occupational stress; stress management interventions

NATURAL HAZARDS AND THE ROLE OF MANGROVES AS A NATURE-BASED SOLUTION FOR COASTAL PROTECTION IN MACAO SAR - Lam, Sut Ieng (University of Saint Joseph, 2023)
The inundation problem in Macao is getting more attention recently, especially after the destructive impacts of typhoons Hato (2017) and Mangkut (2019). The inundation caused by storm surges is getting more severe with the rapid sea-level rise in Macao. Moreover, the potential threat of a tsunami in Macao, may be enhanced with rising sea-level. This research evaluated the risk of coastal hazards in Macao by analyzing the local meteorological data. The results of the analysis indicate a rising trend in the tropical cyclone intensity and more severe storm surges are expected to occur in the future. Moreover, this research explores the potential of Nature-based Solutions (NbS), particularly mangroves, to address the inundation problem in Macao. The study included a preliminary laboratory-based experiment and the application of local mangroves data in numerical models. The results of the experiment and numerical models demonstrate the ability of mangroves to attenuate waves. These findings, although preliminary, indicate that mangroves could be a promising NbS to address inundation issues in Macao. To effectively implement this NbS, further field investigations are needed to measure attenuation in-situ, as well as determine optimal locations for mangrove restoration projects
Keywords: Inundation; Mangroves; Master of Environmental Sciences and Management (MESM); Nature-based solutions; Sealevel rise; Storm surges; University of Saint Joseph; Wave attenuation

EVALUATION OF MANGROVE BLUE CARBON AS A POTENTIAL FOR CLIMATE CHANGE MITIGATION IN MACAU - Lao, Hio Wai (University of Saint Joseph, 2023)
Climate change is a global issue but its impact can be felt locally. Macau SAR has been rapidly developing since the single shift towards a gaming industry-dominated economy, the overwhelming anthropogenic activities contributing to increasing pollution. Mangroves, which play an essential role as the blue carbon system with a high carbon sequestration rate could be a natural base solution to the pollution. This study aims to determine 1) the total organic Carbon (TOC) in the soil of Macau mangrove sites, 2) comparison with the methodology evaluating the organic Carbon, and 3) organic Carbon comparison between Macau and other regions. Soil sampling were processed under the Blue Carbon Initiative guideline, and the samples were divided into two parts for determining the TOC%, combustion method from Hong Kong, and methodology of ashing in our laboratory. The overall estimated TOC% of Macau mangrove sites was 1.29%. There are still a lot of potentials in Carbon storage and for climate change mitigation in Macau
Keywords: Carbon sequestration; Mangroves; Master of Environmental Sciences and Management (MESM); University of Saint Joseph; blue Carbon

THE VALUATION OF MCDONALD’S CORPORATION (NYSE: MCD) - Lao, Hong U. (University of Saint Joseph, 2023)
This paper analyses the valuation of McDonald's Corporation (MCD) as of December 31, 2021. An estimate of the Company's intrinsic value will also be provided. In addition, the internal company factors and external market conditions influencing company valuations and share prices will be discussed. The study has two main objectives: Determine the intrinsic value of McDonald's common stock as of December 31, 2021, and compare it to the actual stock market price on the same date. An assessment of the stock’s market price should represent the Company's true value on that day. Research can then verify whether it was overvalued or undervalued on that day. Identify internal company factors and external market environment factors that affect the Company's operations. This information will be used to gain a deeper understanding of the sensitivity analysis results. Possible scenarios will be discussed to reflect how these factors stimulate macroeconomic, industry, and business developments, as well as the strategic responses of industry players or competitors. McDonald's possible strategic responses to these scenarios will also be assessed. In this paper, a combination of qualitative and quantitative research methods will be employed. Data collection and analyses in Chapters 2 to 5 will use a qualitative approach, which includes data related to McDonald's, industry, and economic analyses. Chapters 5 to 8 will apply qualitative and quantitative data collection and analysis methods. Data will be collected from McDonald's annual report for the fiscal year from December 2017 to December 2021
Keywords: Intrinsic Value; McDonald's; Sensitivity Analysis; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph; Valuation

The Collaboration and Challenges Faced by Therapists within Professional Inclusive Education Teams in Macau =: 澳門治療師在融合教育專業團隊中的合作情況及挑戰 - Lao, Pek San (University of Saint Joseph, 2023)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 合作模式; 團隊合作; 治療服務; 澳門治療師

探討教師及家長視角下澳門推行生命教育之現況 =: EXPLORING THE CURRENT SITUATION OF LIFE EDUCATION IN MACAU FROM THE PERSPECTIVES OF TEACHERS AND PARENTS - Lei, Choi In (University of Saint Joseph, 2023)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 教師自我效能; 生命教育; 親社會行為

FEMALE EMPLOYEES’ PERCEPTIONS OF WORK-LIFE BALANCE AND TURNOVER INTENTIONS IN MACAO - Lei, Hon Nei; Silva, Maria Rita (University of Saint Joseph, 2023)
"This study explored the relationships of work-life balance and turnover intentions of full-time employees in Macao, and role of gender, parenting, and elderly care. Namely: (1) What is the relationship between work-life balance perceptions and turnover intentions? (2) What is the moderating role of gender in the relationship between work-life balance perceptions and turnover intentions? (3) What is the moderating role of parenting (i.e., having children or not) in the relationship between work-life balance perceptions and turnover intentions? And, (4) what is the moderating role of care for elderly family members (i.e., having to provide care or not) in the relationship between work-life balance perceptions and turnover intentions?"
Keywords: Elderly Care; Gender; Parenting; Thesis and Dissertations Master of Organisational Psychology (MOP); Turnover Intention; University of Saint Joseph; Work-Life Balance

Consumer purchase intention towards floral products: a study based on the five consumption values - Lei, Si Nga (University of Saint Joseph, 2023)
This dissertation focused on the consumers’ consumption behavior in Macau flower retailers. It revealed what factors affect consumers’ choice of flower shops during purchase. Also, what contributes to the customers’ loyalty towards a flower retailer by having interviews with the female target groups aged between 20 to 50 who work in the office. This study is important to the flower business owner because the result can allow them to understand the thoughts and feelings of their consumer. By interviewing 11 heavy users of floral products with 16 questions based on the five consumption values, we can communicate with the consumers directly and learn the reasons behind their purchasing behavior. Questions have been divided into 5 consumption values according to the previous research by (Sheth, Newman, & Gros, 1991), including functional, conditional, social, emotional, and epistemic values. The research has collected data on how and at what level these values may affect consumer consumption choices individually. The finding part analyzed the reason why those values affect consumers’ choices. Most of the interviewees stated that service is the most important compared to quality because the owner should be enthusiastic to provide product information and understand the consumer very well to impress and retain them with good personal service
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph; consumption behavior; floral product; purchase intention

INTEGRATING ROBOTS INTO READING IN AN INCLUSIVE ESL CLASSROOM AT LOWER PRIMARY - Lei, Ut Wa (University of Saint Joseph, 2023)
Establishing and improving the independent reading ability of middle school students has become one of the critical topics in the world, especially for second language learners. The cultivation of independent reading ability has specific challenges. This action research investigated the effectiveness of integrating robot-assisted teaching in reading lessons at lower primary grades. A group of third-grade students (n=15) participated in this research. The instruments include the pre-and post-test of a reading competency test (RCT) and motivational index (MI), a teacher reflection journal, and focus group discussion with parents. The whole intervention is conducted in two cycles, and requires the completion of four 40-minute lessons each week per cycle. The findings support the view that integrating robot-assisted teaching in the classroom can improve students' learning motivation to a certain extent, and that intervention programs positively impact students' learning motivation and independent reading ability in English. This study provides suggestion for the design of English reading instruction, and encourages English teachers to pay more attention to improving students' independent reading ability
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; independent reading skills; learning motivation; robot-assisted teaching

職業技術教育導向的特殊教育課程實施成效及其對學生生涯準備的影響之個案研究 =: The Effectiveness of Vocational Education Program for Students with Special Educational Needs and its Impact on their Career Preparation: A Case Study - Leong Hio Man (University of Saint Joseph, 2023)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Promoting Future Elderly Social Participation In Macau: An exploratory Analysis - Leong Kai Chong; Ho, Jacky (University of Saint Joseph, 2023)
"The purpose of the research aimed to explore the challenges and future possiblities of ways of promoting elderly social participation in Macau. As lack of related research has been conduted in Macau, this community services and government policies and to provide suggestions for improving the direction of sustainable development and future possible research topics in this area. The research adopts a qualitative and phenomenological approach to explore the current situations, difficulties and ideas through the industry experience and insights. Nine in-depth interviews with 9 representatives of elderly social service providers subsidised by Macau SAR Government from late April to July 2022 in Macau. The content analysis using open coding to collect inductive data. Throughout themetic analysis identified by four levels: individials, community and social services, governmental policies and infrastructures. Overall, the study found that the autonomy trend of future social participation of the elderly in Macao is enhanced by education and self-health concerns and they are more independent, but the participation of male elders and female elders is unbalanced. Social service providers for the elderly provide a large number of repetitive services and are too passive and dependent on government policies andsupport, resulting in a lack of innovative thinking. The infrastructure design promoted by the government does not consider the continuous health and activity development of the elderly. This study looks at the ability of the elderly in Macau to continue to develop their strengths in the future, and suggests the need to strengthen individual retirement life planning and development for the elderly, personal health monitoring improvement, diversification of social services, elderly-led community programs, private social enterprise capital, and elderly volunteering The urgency of the number of elderly people, more practical and effective elderly inclusive urban planning."
Keywords: Thesis and Dissertations Master of Community Development (MCD); University of Saint Joseph

Do job satisfaction and supervisory support affect burnout among security guards in Macao? - Leong, Chi Ian (University of Saint Joseph, 2023)
We see security guards around in Macao in our daily lives and they are the ones who are responsible for protecting people’s safety and properties. Most security guards are non-local workers and might have different workplace stress levels. This study’s main aim is to investigate how job satisfaction and supervisory support are related to burnout among security guards in Macao. The research is carried out through a quantitative questionnaire to collect data and deliver it to the local and non-local security guards working in Macao. A total of 132 questionnaires were collected. It is expected that when security guards have higher job satisfaction and more supervisory support, they will experience less burnout. This intention enables the organization to make some changes to help the security guards from burnout due to job dissatisfaction and no supervisory support. The practical implication for reducing stress is introducing training courses such as mindfulness-based stress training programs. Future research will investigate other support like organizational support, peer support, and family and friends support on security guards
Keywords: Burnout; Job satisfaction; Supervisory support; Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph

澳門幼稚園非特教專業教師在融合教育班級經營的困難與應對策略之研究 =: Challenges and Strategies in the Management of Integrated Education Classes: Insights from Non-certified Kindergarten Special Education Teachers in Macau - Leong, Choi Cheng (University of Saint Joseph, 2023)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 澳門幼稚園; 班級經營; 融合教育; 非特教專業教師

The VALUATION OF TENCENT HOLDINGS LIMITED - Lo, Hao Weng (University of Saint Joseph, 2023)
This study analyzed Tencent Holdings Limited’s internal and external factors and future strategies, forecasted the financial statements of the Company for the next ten years, and measured the intrinsic value of the Company on December 31, 2021 and compared it with the stock market price on the same date. The share price’s sensitivity analysis was also conducted to understand the Company's capital structure and profitability, and the sensitivity analysis can be used to reflect the impact of these factors and strategies on the future share price, which can have a high impact on investors' future investment decisions. This study also used the SWOT Analysis and Michael Porter's Five Forces Analysis to analyze the Company's strengths, weaknesses, opportunities and threats and the Five Competitive Forces that shape the technology industry to evaluate the Company's external and internal environment and enrich the management with a more intuitive analysis leading to recommendations
Keywords: PEST Analysis; SWOT Analysis; Technology Industry; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A Financial Valuation of Starbucks (SBUX) - Lok, Ka Ian (University of Saint Joseph, 2023)
Starbucks Corporation (hereinafter “Starbucks” or “the Company”) is a worldwide coffee retailer, which operates over 33,000 stores located in over 83 countries nowadays. The purpose of the study is to estimate Starbucks’ intrinsic value as of December 31, 2021 and identify whether the Company was overvalued or undervalued. Several analyses give investors and shareholders an insight into how the Company may develop or identify the ability to generate positive returns from investing in Starbucks. This study is mainly separated into two aspects. The first part specifically discusses the Company overview, industry analysis, and economic outlook, which includes SWOT analysis, PESTEL analysis, Porter's five forces analysis, and value chain analysis to identify external and internal factors that may influence the Company. The second part focuses on financial analyzes, including both historical and forecasted financial statement. Three valuation models and a sensitive analysis are applied to understand the Company’s financial conditions and performance. Starbucks’ intrinsic value is derived from the three discounted cash flow models, indicating the market overvalued the Company’s stock price as of December 31, 2021. Finally, investors and shareholders can understand more about Starbucks’ capital structure, financial highlights, and intrinsic value, because this set of information is critical for existing investors and potential investors to make investment decisions
Keywords: Starbucks; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph; financial valuation; value valuation

MONITORING THE CONCENTRATION OF PARTICULATE MATTER (PM10 AND PM2.5) IN SEVERAL ROADSIDE LOCATIONS IN MACAO - Ma, Fa Chong (University of Saint Joseph, 2023)
Road transportation is one of the main sources of air pollution in Macao. This study mainly explores four major roadside locations with high traffic flow in Macao from March to May 2022 and measures their pollutant concentrations (PM10 and PM2.5), traffic flow and their fuel type, as well as considering the meteorological parameters and pollutant concentration of SMG Macao to analyze the relationship between traffic flow and pollutants on roadside locations. Under the measuring distance between 3 and 6 meters, showing that the four locations had a good correlation with the roadside station data provided by SMG on both weekdays and weekends/holidays (PM2.5: R2 is 0.59 to 0.81 on weekdays and 0.79 to 0.88 on weekends/holidays, p<0.01; PM10: R2 is 0.33 to 0.82 on weekdays and 0.30 to 0.58 on weekends/holidays, p<0.05), the overall PM2.5 is 41 to 86% higher than that of the same period of Macao roadside station (SMG), and 68 to 186% higher than that of Taipa Ambient (SMG), indicating that it is more harmful to daily pedestrians. The overall relationship between PM concentration and traffic flow is small on the long-term scale (PM2.5: R2 is 0.01 to 0.13; PM10: R2 is 0.00 to 0.02). This study also analyzed air quality on EBL, the overall PM2.5 and PM10 decreased by 12.3% to 24.8% compared with non-EBL during the period, so that is indeed beneficial to the reduction of pollutant concentrations. In addition, narrower roads were overall higher when road widths added for comparison. Lastly, meteorological data added for comparison, except for relative humidity, it can be found that there is a significant correlation with long-term pollutants (p<0.05). While previous studies have found that single-day traffic flow is related to the increase in PM concentration, this paper is more inclined to their two-way effect when exploring their long-term relationship
Keywords: Thesis and Dissertations Master of Environmental Sciences and Management (MESM); University of Saint Joseph; air pollution; monitoring campaign; particulate matter; traffic characterization

Investigating the influence of Instagram on the local foodservice sector in Macau: A Consumers' Perspective - Mac, Hoi Kuan (University of Saint Joseph, 2023)
Nowadays marketers and practitioners recognize the importance of social marketing as a strategy to acquire customers. Accordingly, the enterprises and brands are embracing the use of social network in communicating with potential consumers ad actual consumers, in order its performance so as to increase its sales. Among all those social media platforms, Instagram is one of the platforms which is image orientated and can easily connect with users and provide information with photos and images. As Macau is small‐sized city where there are abundant small to medium‐sized enterprises, the local small firms are switching their marketing strategies by utilizing the Instagram to promote their product online. In order to get a better grasp of how Instagram affects the promotion of the food and beverage product in Macau, the research question has been formulated: “To what extend can the local food sectors in Macau use Instagram as a marketing tool to engage purchasing intention and strengthen their brand equity? From the perspective of customers.” Semi‐structured interviews were conducted with 13 participants who are the Instagram users, with diverse situations of engagement on Instagram. According to the interviews, participants expressed that how Instagram can associate effects with arousal and brand equity (brand awareness, brand image, perceived quality and brand loyalty) and formation of purchase intention eventually through the Instagram marketing activities. The results showed that Instagram marketing activities strongly correlated the brand equity (brand awareness, brand image, and perceived quality while which in turn led to purchasing intention towards the brand. This research comprehensively illustrates the influences of Instagram marketing activities on customer‐based brand equity. The findings of this study will enable local food brands to more accurately forecast the future purchasing behaviors of their customers through Instagram marketing activities and provide a guide in managing brand equity as well
Keywords: Brand Equity; Instagram; Purchase Intention; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Can The Organisation Help? Exploring The Relationship Between Emotional Intelligence, Resilience And Burnout Among Counselling Professionals With Organisational Socialisation As Moderator - Mak, Sin Kei (University of Saint Joseph, 2023)
The phenomenon of burnout has been recognised as a worldwide occupational health issue after being vastly studied for decades. Trait Emotional Intelligence (trait EI) and resilience have been identified as personal protective factors (Gutierrez & Mullen, 2016; Listopad et al., 2021), while organisational socialisation is suggested to be an organisational factor in helping people in preventing burnout (Taormina & Law, 2000). With the purpose of 1) investigating the phenomenon in the counselling profession, as well as 2) exploring how trait EI and resilience are related to burnout and whether organisational socialisation might impose moderating effects in between, the present study examined 115 counselling professionals currently employed and working in organisational settings in Macau by snowball sampling, using a quantitative and cross-sectional approach through self-reported online questionnaires. From the data obtained, different burnout patterns were observed according to job titles and work settings, indicating that counselling professionals with different specialties and work in different settings have unique sources of stress, which resulting in differences in their burnout patterns. No between-group differences were observed in age and work experience, while male participants have a higher burnout perception than female participants in the current study. On the other hand, current results suggested trait EI and four components of resilience (determination, endurance, adaptability and recuperability) are negatively correlated to counselling professionals’ burnout perception, providing supportive evidence that trait EI and resilience are protective factors against burnout. Moderation analysis results revealed that organisational socialisation has some moderating effects on the relationship between trait EI, resilience and burnout. However, differences in direction and intensity indicated that the moderating effects of organisational socialisation might be influenced by individual differences. Further studies are needed to better the understanding of the moderating effect of organisational socialisation. Limitations of the current research and implications for counselling professionals and organisations were also discussed in the study
Keywords: Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph; burnout; counselling professionals; organisational socialisation

A FINANCIAL VALUATION OF ORACLE CORPORATION - Maung, Ye Thu Anug (University of Saint Joseph, 2023)
Oracle Corporation (hereinafter referred to as Oracle, ORCL, or ‘the Company’) is an American multinational company that provides solutions of products and services that serve the enterprises’ information technology (IT) environment. This thesis is to conduct a business analysis of the Company from a financial perspective, determining the Company’s intrinsic value as of May 31, 2021, and comparing it with the respective market value. Thus, this thesis will study, evaluate, and present an overview of the Company, an analysis of the Company’s market, industry, strategy, financial performance, including external and internal factors, a ten-year pro forma financial statement forecast, and the techniques of using the three discounted cash flow models to estimate the intrinsic value of Oracle. The obtained results from the three valuation models, including the Enterprise Discounted Cash Flow (EDCF) model, the Adjusted Present Value (APV) model, and the Discounted Economic Profit (DEP) model, show that the Company’s intrinsic values were estimated at $74.57, $75.21, and $74.82, respectively. When the results were used to compare with the market price of Oracle’s shares as of May 31, 2021, at $78.74, it reflects that the Company was overvalued
Keywords: Analysis; Financial Valuation; Oracle Corporation; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

MULTICULTURAL CAREGIVER TEAMS IN ELDERLY CENTRES IN MACAO: COMMUNICATION AND PERCEIVED SERVICE QUALITY - Mejia Dominguez, Victor Alejandro (University of Saint Joseph, 2023)
This study explored the effect of communication (i.e., among staff, and between staff and clients) and of cultural diversity on job satisfaction (i.e., intrinsic, extrinsic, and general) and perceived service quality of formal caregivers working in elderly services in Macao. We applied a quantitative methodology, based on a cross-sectional design using a self-response questionnaire to 162 staff in six elderly centres in Macao. Based on an extensive review of the literature, we proposed that: H1) cultural diversity is negatively related to (a) intrinsic job satisfaction, (b) extrinsic job satisfaction, (c) general job satisfaction, and (H5) negatively related to perceived competence and service quality; (H2) communication (a) among staff and (b) between staff and clients is positively related to intrinsic job satisfaction (H3) extrinsic job satisfaction, (H4) general job satisfaction, and (H6) perceived service quality; and finally that (H7) intrinsic, (H8) extrinsic, and (H9) general job satisfaction mediate the relationship between (a) cultural diversity, (b) communication among staff and (c) communication between staff and clients, and perceived service quality. We found that more communication among staff was related to higher intrinsic, extrinsic and general job satisfaction, and perceived competence and service quality. And intrinsic job satisfaction mediated the positive effect of communication among staff on perceived service quality. Opposite to predicted communication between staff and clients was related to lower levels of job satisfaction. And cultural diversity was positively related to satisfaction, as well as perceived competence and service quality. The theoretical and practical implications of findings, as well as limitations and suggestions for future research were discussed
Keywords: Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph; caregivers; communication; elderly services; job satisfaction; multicultural teams; service quality

Macau Ambient Air Pollutants Forecasting By Pollutant Time Series And Meteorological Data Using Machine Learning Methods - Ng, Chung Wang (University of Saint Joseph, 2023)
" Air pollution in Macau has become a serious problem following the Pearl River Delta’s (PRD) rapid industrialization that began in the 1990s. While there has been continual improvement in recent years, harmful air pollutant concentration levels are still common, impacting Macau residents' health and creating long-term medical costs to local society. With this in mind, Macau needs an air quality forecast system that accurately predicts pollutant concentration and an early alert system instead of only daily real-time reminders. Some scholars have previously carried out studies to develop an air quality forecast for Macau by successfully using statistical models. Therefore, pursuant to the outcomes of previous studies, this dissertation aims to build upon research results and explore further possibilities of building a better ML air quality forecast model based on the time series of air pollutants concentration and meteorological data. Four different state-of-the-art ML algorithms were used to create predictive models to forecast PM2.5, PM10, and carbon monoxide (CO) concentrations for the next 24 and 48-hour. These were Support Vector Machine (SVM), Artificial Neural Networks (ANN), Random Forest (RF), and Extreme Gradient Boosting (XGBoost). In addition, Multiple Linear Regression MLR, a standard ML model, was used for this dissertation as a baseline reference for performance comparison. The daily measurements of air quality data in Macau from 2016 to 2021 were collected for this dissertation. The 2020 and 2021 datasets were used for model testing while the four-year data prior to 2020 and 2021 were used to build and train the ML models. The results showed that SVM, ANN, RF, and XGBoost were able to provide a very good performance in building up a 24-hour forecast with higher R2 and lower RMSE, MAE, and BIAS. Meanwhile, all ML models in 48-hour forecasting performance were satisfactory enough to be accepted as a two-day continuous forecast even if the R2 value was lower than the 24-hour forecast. The 48-hour forecasting model could be further improved by proper feature selection based on the 24-hour dataset, using the SHAP value test, and the adjusted R2 value of the 48-hour forecasting model."
Keywords: Air pollution; Macau; Machine Learning; Meteorological features; Thesis and Dissertations Master of Environmental Sciences and Management (MESM); Transboundary pollutants; University of Saint Joseph

澳門小學非特教專業教師對融合教育之態度研究 =: A study on the Attitudes of the Non-specialized Teachers of Primary Schools in Macau towards Inclusive Education - Ng, Ka Man (University of Saint Joseph, 2023)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 小學; 融合教育; 非特教專業教師

INFORMAL RECYCLING IN MACAU: CHALLENGES AND OPPORTUNITIES FOR SUSTAINABLE DEVELOPMENT - Ng, Sut Wa (University of Saint Joseph, 2023)
Informal recycling plays a crucial role in municiapl solid waste management in many cities, particularly in the global South. This study examines the practices, challenges, and opportunities of informal recycling in Macau, a small city and Self Autonomous Region (S.A.R.) in China. Using qualitative research methods, including semi-structured interviews, this study explores the motivations and strategies of informal recyclers, the challenges they face, and the potential for collaboration with formal waste management systems. The findings of this study reveal that informal recycling in Macau is a complex and multifaceted reality and practice that involves a range of actors, from waste pickers to small-scale processors to exporters, all with their specific challenges. Informal recyclers are motivated by economic necessity, and they employ a variety of strategies to collect and process recyclable materials. However, they also face significant challenges, including high rental and transportation costs, lack of manpower, China’s waste import policies and ensuing restrictions, fluctuating global price rates of materials and the unstable income as serious consequence, accompanied by limited support from the local Government. This study also identifies opportunities for sustainable development of informal recycling in Macau, supported by the analysis of data collected via questionnaire survey regarding Macau citizens’ waste separation habits and their willingness to pay for resource separation and recovering process. The identified oppurtunities include establishing partnerships between informal and formal waste management actors, improving the infrastructure, and introducing environmental levy system and consistent policies and regulations. Overall, this study contributes to a better understanding of the role of informal recycling sector in waste management in Macau and provides insights into potential strategies for improving the sustainability of resource and waste management practices in the city
Keywords: Circular Economy (CE); Informal Recycling; Integrated Solid Waste Management (ISWM); Recycline Rate; Sustainable Development Goals (SDGs); Thesis and Dissertations Master of Environmental Sciences and Management (MESM); University of Saint Joseph; Waste Hierarchy

學以致用中文課程（演講）對疑似中文資優學生中文素養提升之研究 ——以澳門某中學高中學生為例 =: A Study On The Improvement Of Chinese Literacy Of Suspected Gifted Chinese Students In The Course Of Learning-to-Use Chinese (Speech) – Taking Senior High School Students Of A Middle School In Macau As An Example - O, Chi Wa; 姚小雪 (University of Saint Joseph, 2023)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 中文素養; 學以致用中文課程; 演講; 疑似中文資優; 資優教育

The Spread of Buddhism in Japan and The Spirit of Japanese Tea Ceremony - Rosa, Alfredo Augusto da (University of Saint Joseph, 2023)
Buddhism was founded by Shakyamuni, and this religion has appeared in opposition to Brahmanism's caste system since its inception. Shakyamuni emphasized the important concept of “all beings are equal” from the very beginning. Buddhism spread from India to other regions, and was introduced to China through Central Asia. In China, Buddhism merged the two native cultures of Confucianism and Taoism and finally produced the socalled Chinese Buddhism. Buddhism and its value of equality were also developed and extended in China, and finally spread to Japan. After Buddhism was spread to Japan, it developed rapidly due to official support. Different Buddhist sects have established their own temples in Japan, and among them, Zen Buddhism has the greatest influence among all social classes in this country. Later, after years of development, Zen Buddhism penetrated into many aspects of Japanese culture, such as religion, aesthetics, garden design, samurai spirit and tea ceremony. With the spread of Zen Buddhism, the core value of Buddhism which is “Buddhist concept of equality” was also spread to Japan. The tea ceremony is precisely the place where this value of equality can be detected. This dissertation explains the many processes that reflect this value no matter inside or outside the tea room, and argues that the spirit of the tea ceremony is to pursue the value of equality
Keywords: Buddhism; Equality; Tea Ceremony; Thesis and Dissertations Master of Philosophy (MPH); University of Saint Joseph

SOCIAL PERSPECTIVES ABOUT CANTONESE OPERA IN MACAO ACROSS GENERATIONS: CULTURAL IDENTITY AND SOCIAL BONDING - Sin, Shuk Ching; Silva, Maria Rita (University of Saint Joseph, 2023)
"Cantonese opera (CO) represents an art form that had its golden time in Macao during the mid-twentieth century. CO still has many loyal fans but they mainly are in the older generation. The purpose of this study was to explore if CO is considered a cultural capital heritage in Macao, related to cultural identity and transmitted across generations to support social bonding. Applying a qualitative methodology, a script for exploring participants’ experiences and opinions about CO was designed, and different groups of individuals were recruited for semi-structured interviews and focus groups. The data collected was analysed by a thematic analysis of the verbatim transcripts. Findings show that in the past first contacts with CO happened in family and related social context, mainly during participants’ developing age. However, currently CO is no longer passed on to the next generation. Despite that the young generations acknowledging their cultural identities in CO, mainly in terms of Cantonese culture and Cantonese language, older individuals engaged with CO seemed to perceive their cultural identities more in depth in its history, literacy and music. Actually, engagement is an important factor that generates social bonds. The CO leisure practitioners, no matter young or old, experienced the effects of social bonding during the ritual of enquiry in the process of learning and practising CO. To improve CO’s preservation in Macao, the adoption of strategies such as developing new productions, crossover with other media, innovations in promotion targeting the young audiences, and absorbing audiences in the Great Bay area were proposed. Finally, the potential use of CO as a tool in counselling and community work is discussed. "
Keywords: Cantonese Opera; Cultural Identity; Individual Well-being; Social Bonding; Thesis and Dissertations Master of Counselling and Psychotherapy (MCP); University of Saint Joseph

A financial Valuation Study for Moody’s Corporation - Sio, Lai Teng (University of Saint Joseph, 2023)
This study presents the intrinsic value of Moody’s Corporation, a leading credit rating agency in the U.S. The results of the valuation were compared to the market value of Moody’s Corporation of the same date. The aim of the research is to provide a perspective to the investors on whether the actual value of the Company was overvalued or undervalued in the market, and how much the volatility of the stock price by the change of some factors. Both qualitative and quantitative analyses were applied in the research. The historical data, economic outlook, and the Company’s strategies were collected to be the metrics to determine the intrinsic value and provide an analysis of the prospects of Moody’s Corporation. Three valuation models were applied in the research to estimate the intrinsic value of the Company’s common stock. The cost of debt, cost of equity, the weighted average cost of capital, and the market risk premium were introduced and calculated in the research as they were the critical components in the valuation process. Since the valuation was based on assumptions and historical data to determine future growth, which indicates that the results could be changed due to uncertain factors. This study demonstrates that there was some discrepancy between the stock’s market price and the intrinsic value per share of Moody’s Corporation as of December 31, 2021
Keywords: Intrinsic Value; Moody's; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph; Valuation

Assisting the Creative Processes in Visual Merchandising for Luxury Fashion Retail - Soares, Patricia Alexandra Ferreira (University of Saint Joseph, 2023)
This dissertation aims to research the need and viability of creating a digital platform that assists the creative processes naturally linked to Visual Merchandising. Through the proposal of a digital platform that works as a co-creative tool for display archives and a co-creative tool for display set-ups through mood boards, we will aim at improving the teamwork in retail and provide a unique, fast-forward platform for information sharing and input under the direction of Visual Departments. Building on rich source materials such as bibliography, scientific papers, news, and articles, and interviewing Visual Merchandisers actively working in the field, we will show the importance of creativity in Luxury Retail and what are the most common challenges in the field that we will propose a solution to. We will focus on the study of concepts, reviewing digital application tools being used by professionals and their best features and improvement opportunities. By gathering this information, we hope to provide accurate insights and information that proves the viability of this proposal and understand what features could serve best the target audience. Finally, we will present a conceptual idea in the form of sketches with functions of this digital application tool to be fully developed in the future and hopefully build a consistent well, designed commercial web-based application
Keywords: Luxury Retail; Thesis and Dissertations Master of Design (MDG); University of Saint Joseph; VM Digital Platform; VM Display Archives; VM Moodboard; Visual Merchandising

Emotional Support Influence Work Engagement and Mental Well-being in Macau: The Moderating Effect of Self-reflection - Sou, Kam Chan; Kuok, Angus C. H. (University of Saint Joseph, 2023)
The purpose of this study is to examine work engagement and mental well-being in Macau, specifically after more than three years of COVID. Examine whether external factors such as emotional support from supervisors, co-workers, and family members have a positive impact on work engagement and mental well-being, and whether the internal factor self-reflection with its three aspects of need for self-reflection, engagement in self-reflection, and insight from self-reflection moderates the relationship between emotional support, work engagement, and mental well-being. The target audience consists of Macau's integrated resort, hospitality, and gaming industry employees. According to the Affective Event Theory (AET), affective events at work generate emotional responses that influence the attitudes and behavior of employees in the workplace. In this study, this theoretical framework was used to clarify the interplay of variables that explain emotional support from supervisors, co-workers, and family members, work engagement, and mental well-being. An online self-response survey (N=325) was used to conduct quantitative and cross-sectional research. There was also a combination of simple random sampling, convenience sampling, and referral sampling. All variables were found to be correlated, and while perceived supervisor support was a significant predictor of all aspects of work engagement and mental well-being, family and co-worker support only predicted certain aspects of these variables. Self-reflection partially moderated the positive effects of certain emotional support on work engagement and mental well-being
Keywords: Co-worker Support; Emotional Support; Family Support; Mental Well-being; Perceived Supervisor Support; Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph; Work Engagement

LEADERSHIP STYLE AND ORGANIZATIONAL CULTURE INFLUENCE ON EMPLOYEES’ ORGANIZATIONAL COMMITMENT UNDER THE PANDEMIC SITUATION - Sun Leung, Wai Chai (University of Saint Joseph, 2023)
The aim of this study is to investigate the influence of leadership styles and organizational cultures to employee’s organizational commitment under the pandemic situation in Macao. The dependent variables comprise of the three dimensions of organizational commitment. Among those three, affective commitment and continuance commitment are considered to be analyzed in this study. The leadership styles concept and organizational cultures are applied as the independent variables. The objectives are achieved using quantitative research method with questionnaires in Likert scale scores. The two significance reveals that laissez-faire leadership style had a positive relationship with continuance organizational commitment (H4) and innovative culture had a positive correlation with continuance organization commitment (H6). Such outcomes were extended to a qualitative study with qualitative approach on discourse analysis to explore the potential factor and a leadership discourse analysis was initiated. While the findings on influence of leadership and culture on organizational commitment is not a major concern for Macao employees in the pandemic situation, the significance of specific leadership style and culture rationalizes the transformation and status of Macao employees’ views towards leadership and employers’ perspective on organizational culture. The data collected in this study may also provide valuable resources for future study and training programs for the coming batch of employees in the coming new phase of Macao in entering the 2nd round of gaming licensing. Create the right leadership and culture for the organization to bring back the passion of Macao employees
Keywords: Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph

融合班中特殊教育需求學生和普通學生共同學習的過程與效果﹕來自老師和家長的反饋 The Process and Effects of Collaborative Learning of Students in Inclusive Class: Voices from Teachers and Parents - Tam, Sin Leng (譚倩鈴) (University of Saint Joseph, 2023)

THE RELATIONSHIP BETWEEN PARENTING STYLES, ACADEMIC ACHIEVEMENT AND BEHAVIORAL PROBLEMS OF PRIMARY STUDENTS IN MACAO - Tang, I. Sam (University of Saint Joseph, 2023)
"Parenting styles may have various effects on children’s development and educational outcomes, particularly a relationship with behavioral problems and academic achievement. This study examines the relationship of between parenting styles, behavioral problems and academic achievement. A cross-sectional and questionnaire-design (Parenting Style Scale (Saunders et al., 2013); Strength and Difficulties Questionnaire (Goodman & Goodman, 2009; Goodman, 1999; Goodman, 1997)) study was used with a sample total of 98 parents with the eldest child of the family aged between six to twelve. Results of the findings are mainly inconsistent with the majority of literature. Indulgent and authoritative parenting are the predominant parenting styles, yet parenting styles does not relate to academic achievement. On the other hand, the correlation between behavioral problems, specifically prosocial behaviors and academic achievement are moderate. Furthermore, there is no difference between the type of behavioral problems according to gender. In further studies, a larger sample size, teachers and students as informants, and the inclusion of the analysis of other factors that could be influencing parenting styles, behavioral problems and academic achievement are suggested to be considered. "
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

UNITING - FRAGMENTED SPACES ARCHITECTURE CENTRALIZING HERITAGE INTERPRETATION - Un, Cheng Wai (University of Saint Joseph, 2023)
For many people, an art museum is a place to display artifacts, artworks, and the temporaryhistory of a community or country. It also advocates for an artist’s viewpoints on art. In fact,museum design is closely related to politics. The purpose for building a museum in a city is toexhibit information about the development of the local culture. Moreover, high culturalvalue land is usually built with museums displaying their heritage nearby, so that people canexplore and learn more about the local historical background and artifacts of the place.The abandoned Iec Long Firecracker Factory in Taipa Center, Macau has been on hold formany years and has also been used as a war game venue that resulted in scratches on thewalls of the dilapidated old heritage buildings. Recently, the Macau government has finalizedits plans for the revitalization of this local heritage site. Due to its dispersed layout andsurrounding landscape, there are some design constraints around the preservation of thisimportant heritage site. The design for high cultural value land should not only consider thepreservation and renovation of old buildings but also consider more ways to effectively usethe site as an important public venue for the city.For developing the methodologies of this project, several concepts and case studies wereanalyzed to extract ideas that can be referenced and to unveil strategies for designing apossible solution to this problem. This dissertation intends to create a model for developingand integrating architectural design into this heritage site and will study the spacearrangements for both the indoor space and the outdoor space within the concept of afragmented space integration. Fragmented space, means that a place is designed using adecentralized layout. This conceptualization of a design can preserves the original appearance of the cultural value of land and at the same time, the space can be used moreefficiently to create a circulation for the public to visit and enjoy the location
Keywords: Theses and Dissertations Master of Architecture (MARCH); University of Saint Joseph; articulation architecture; decentralized layout; functional museum; integration with architecture; spatial narrative

THE EFFECTS OF TEACHER SELF-EFFICACY AND PERCEIVED AUTONOMY ON TEACHER WORK ENGAGEMENT: THE MEDIATING EFFECT OF PERCEIVED ORGANISATIONAL SUPPORT - Wan, Sok Leng (University of Saint Joseph, 2023)
The aims of the present study are to investigate the level of work engagement of the inclusive teachers in Macau and what potential factors would contribute to the increase of their level of work engagement. In this research, the framework of the self-determination theory developed by Ryan and Deci in 2000 was partially employed. I suggested the inclusive teachers’ self-efficacy and perceived autonomy to act as the independent variables, while perceived organisational support was involved as the mediating variable. Quantitative method was applied in this study by using an online self-response questionnaire (N= 150). The stratified sampling strategy was applied as well in order to ensure the representativeness. No gender difference of work engagement level was found among Macau inclusive teachers. Positive correlations were found among all variables. Besides, perceived organisational support was expressing positive mediating effects on the relationships between independent and dependent variables under some specific circumstances. For example, the relationship between efficacy to use inclusive instructions and emotional and physical work engagement; the relationship between perceived autonomy and cognitive, emotional, and physical work engagement. Theoretical and practical implications for the non-tertiary schools and inclusive teachers can be found in this study. Future studies should be continued to investigate the limitations and suggestions of this field of research
Keywords: PERCEIVED ORGANISATIONAL SUPPORT; TEACHER PERCEIVED AUTONOMY; TEACHER SELF-EFFICACY; Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph; WORK ENGAGEMENT

Study on User Acceptance on Customer Behavior for Online Payment in Macau: MPAY Case Study - Wong, Chi Cheng (University of Saint Joseph, 2023)
With the rapid expansion of mobile e-commerce, an increasing number of businesses have jumped into the fray in all facets of the mobile electric commerce industry chain. The payment link is the most competitive. From the norm in the sector to the consumer market, telecom operator rivalry, as well as third-party payment between different companies, never ceases. In the context of mobile e-commerce, however, competition has shifted from traditional product-centered to customer- centered, and business success frequently rests on the customer. As a result, the competition in the mobile e-commerce payment industry is essentially about competing for users. Mpay is characteristic of mobile e-commerce payment firm representatives; on the basis of theoretical analysis, combined with the reality of the economic background, the study chose Mpay mobile payment users as research subjects and analyzed the major variables of user acceptability. The model was built on the basis of an extensive evaluation of past research results of user acceptance model and reference to UTAUT model. The model considered performance expectancy, effort expectancy, and social influence, facilitating condition as independent variables determining user behavior intention, Based on the conceptual model, the paper conducted an empirical investigation as a case study of a Mpay mobile payment user using data from a questionnaire, while also conducting a separate discussion of the impact of perceived risk and trust on user acceptance. The empirical results indicate that for mobile payment users, performance expectancy has the greatest positive effect on behavior intention, while facilitating conditions, social influence, perceived risk, effort expectancy, and trust have no effect. In addition, gender and age were discovered to influence user acceptance
Keywords: Online mobile payment; SmartPLS; Thesis and Dissertations Master of Business Administration (MBA); UTAUT model; University of Saint Joseph; user acceptance

PROJECT MANAGEMENT ADOPTION AND MATURITY LEVEL IN INFORMATION TECHNOLOGY INDUSTRY OF MACAU AND HENGQIN - Wong, Ka Seng (University of Saint Joseph, 2023)
Projects are tactical and operational initiatives, and achieving specific outcomes through projects can help organizations achieve strategic goals. The effective use of project management tools and techniques is essential to achieve successful results, since the goal is to maximize the realization of the project's plan by effectively using the budget, time, and resources provided by the project owner to achieve the project's original purpose. The Project Management Maturity Model (PMMM) is a tool for measuring project management capabilities and is essential to improve project and portfolio performance in different industries. The main objective of this research is to analyze and characterize the maturity level and capacity of the IT industry in Macau and HengQin based on the assessment of the PMMM. The research also aims to assess and compare the maturity level in the IT industry in Macau and HengQin. An online survey was conducted and sent to IT project managers from Macau and HenqQin. A total of 34 responses were collected, divided into 3 different parts: Part I - General Information, Part II - Project Management Areas, and Part III - Perception. The results indicate that, in general, Project Managers state that their companies do not follow Project Management standards and best practices, classifying as Low and Very Low essential PM areas such as Planning and Scheduling (68%), Scope (61%) and Communications (64%). From a comparison perspective, project managers in Macau follow less formal frameworks than Hengqin in managing the triple constraints of the project. The collected data also indicate that Macau's communication management and stakeholder engagement are less mature than Hengqin's. Furthermore, the data indicate that maturity level is not necessarily related to education level, which means not higher education has a higher maturity level. Recommendations are provided for the IT industry in both areas, and specific comments are provided for each group or professionals. In conclusion, this work allows a novel characterization and a better understanding of the Project Management adoption and maturity level of the IT Industry in Macau and Hengqin
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph; information technology; maturity level; project management; project management maturity model; project maturity assessment

自閉譜系障礙之兒童透過即興劇表達社會情感之個案研究 =: A case study on using drama improvisation as a social emotional intervention for a child with ASD - Wong, On Na; Ho, Ka Lee Carrie (University of Saint Joseph, 2023)
"Abstract The core concept of drama education is the integration and int- ernalization of experience. In the empirical content of the improvis- ational drama, it lays a profound foreshadowing for future life prac- tice through different physical behaviors and facial perceptions. Through drama education, children with autism spectrum disorder can be emotionally adjusted. Emotional and social behavior is essent- ial for children with autism spectrum disorders. The use of improvis- ational drama to study children's emotions with autism spectrum diso- rders is not yet found in Macau. Therefore, this study aimed to inve- stigate the intervention strategies for children with autism spectrum disorders through improvisational drama to fill the research gap. A case study of emotional interventions as a ten-day improvisa- tional drama with an autism spectrum disorder in Macau. The following findings were obtained: 1. The study found that improvisational drama was used to address the theoretica deficits of the mind of children with autism spectrum disorders. 2. Improvisational drama supports the understanding of self-emotions in children with autism spectrum disorder with positive behavior. 3. Shared attention cultivated by improvisational drama can develop social interaction behavior. 4. The improvisational drama techniques can deal with children with autism spectrum disorder and peer conflict. Based on these results, the researcher identified three main is sues in the use of improvisational drama to deal with the emotions of VII children with autism spectrum disorders in Macau: 1. The relative lack of knowledge on the use of improvisational drama as a strategy to support children with autism in Macau. 2. The number of hours and sessions of the Macao training course is too small to be satisfied with frontline teachers' use of improvi- sational drama to provide quality teaching to children with an au- tism spectrum disorder. 3. Failing to understand the emotional needs of children with autism frontline teachers must practice improvisational drama teaching, failing to understand it’s core subjects in depth. Therefore, researchers on the emotions of children with an aut- ism spectrum disorder in improvisational drama. The proposal is divi- ded into three main areas, which are proposed to the government, sch- ools, and teachers: I. Suggestions to the government: 1. Improve the special education policy 2. Increase the number of training courses II. Suggestions for schools: 1. Increase the teaching content of the curriculum for children wi- th autism spectrum disorders III. Suggestions for teachers: 1. Children should lead the curriculum with autism spectrum disord- ers. 2. The curriculum should enhance the cooperation between children VIII with autism spectrum disorders and their peers. This study has identified feasible intervention strategies to he- lp further improve the Macau government's special education policy. The study also aims to help schools to adapt their teaching cont- ents better to suit the needs of children with autism spectrum disord ers. Finally, the study aims to provide teachers with a better unders- tanding of the characteristics and social-emotional behaviors of ch- ildren with autism spectrum disorders to help each other practice education effectively. Only one child with autism spectrum disorder were studied in Mac- ao. As a result, this study failed to represent all children in Macao in practicing emotional interventions in improvisational drama. This study aimed to promote -improvisational comedy strategies in Macau to help children with aut-ism spectrum disorders to understand and expre ss their emotions appr-opriately. It is also expected that the Macau SAR government will re-cognize the importance of drama education for children with autism spectrum disorders and develop policies and ada- pt the content of the curriculum framework to enable the effective i- mplementation of drama education in teaching emotions to children wi- th autism spectrum disorders."
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 即興戲劇; 情緒; 戲劇教育; 自閉譜系障礙兒童

Evaluating the Acceptance of Portuguese Residents Towards Chinese Electric Vehicles: the Role of the Country-of-Origin Effect - Xian, Si Tong (University of Saint Joseph, 2023)
This study identifies Portuguese residents’ behavioural intention towards Chinese electric vehicles from the perspective of the Country-of-Origin Effect (COE) and uses the Unified Theory of Acceptance and Use of Technology 2 (UTAUT-2) as a guide to design interview questions. According to the existing literature, UTAUT-2, a comprehensive technology acceptance model, has not been used to assess the Portuguese electric vehicle market, and no relevant research has been found to apply the method of combining the COE into the UTAUT-2 framework. The purpose of this study is exploratory in nature, it uses qualitative methods to identify the behavioural intention of Portuguese residents towards the acceptance of Chinese electric vehicles. Data from 16 Portuguese residents was collected through semi-structured interviews and analyzed with qualitative methodology. The study found that factors such as performance expectations, environmental concerns, effort expectations, hedonic motivation, and social influence have a positive impact on Portuguese residents' purchase of electric vehicles, while price value, habits, and convenience conditions have a neutral or negative impact. Regarding COE, apart from social influence, it has no impact on other factors. To increase the popularity and sales of Chinese electric vehicles in Portugal, it is recommended that advertising and marketing efforts focus on price, charging services, after-sales service, and design
Keywords: Consumer Behavior; Country of Origin Effect; Electric Vehicles; Environmental Awareness; Portugal; Sustainability; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

將CRA教學法融入澳門小學融合班數學課程 之行動研究-以二年級兩位數減法單元為例 =: An Action Study of Integrating Concrete-to-Representational-to-Abstract (CRA) into the Mathematics Learning of Integrated Classes in Macao Primary Schools - Taking the Two-digit Subtraction Unit of Grade 2 as an Example Concrete-to-Representational-to-Abstract (CRA) - Zhuang, YanYan (University of Saint Joseph, 2023)
Keywords: CRA教學策略; Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 兩位數减法; 小學數學課程; 融合生; 行動研究

EDUCATORS' PERSPECTIVE OF STUDENTS WITH SPECIAL EDUCATIONAL NEEDS (SEN) AND THEIR SENSE OF BELONGING, SELF-COMPETENCE, AND AGENCY - Carvalho, Edna Line Henriques de (University of Saint Joseph, 2024)
What strategies did educators use to cultivate a sense of belonging, self-competence, and agency among students with Special Educational Needs (SEN)? Did educators face any challenges in implementing these strategies? Were the findings of this study specific to the inclusive school in Macau, or can they be generalised to other educational settings? This study brings to light educators' inner perspective of students' sense of belonging, self-competence, and agency. Specifically, it aims to uncover the academic and emotional needs of students with SEN and the importance that these may have in promoting a positive educational experience. By gathering the perspectives of educators in an inclusive school in Macau who work side-by-side with these students daily, we can understand how essential these elements are in contributing to their overall development. The purposive sampling approach was used in this study to further investigate various experiences and perspectives of educators within an inclusive classroom setting. The educators interviewed provided insight into an inclusive classroom with students with SEN in full-time attendance. The educators sampled in this study facilitated the search for strategies, challenges and support systems to cultivate a sense of belonging, self-competence and agency, among students with SEN. Findings showed educators' understanding of the importance of students with SEN's sense of belonging, self-competence and agency. The educators' awareness of their students' interactions with peers, and the educators themselves, was prominent, revealing how the sense of belonging for students with SEN affected these relationships. Regarding students' sense of self-competence, according to educators, students with SEN had opportunities to showcase their confidence in specific classroom areas and to exercise independence in the classroom, within the set curriculum and lesson plans. In the findings, educators illuminated the importance of agency in students with SEN. However, they were apprehensive about changes in lesson plans, cultivating a fully independent classroom setting and providing choices to students with and without SEN. The study's implications highlight the educational practices and policies that effectively supplement students with SEN's academic and social environments. The findings of this study aim to guide curriculum developers, educators and parental figures in fostering positive learning experiences for students with diverse learning needs
Keywords: Heutagogy; SEN; Self-competence; Students' agency; Thesis and Dissertations Master of Education (MED); University of Saint Joseph

PSYCHOMETRIC PROPERTIES OF BASIC FAMILY RELATIONS INVENTORY (BFRI) IN MACAO - Chan, Kuai Ian (University of Saint Joseph, 2024)
By discussing various aspects of family functioning, including the intricate nature of family functioning, family dynamics’ impact on adolescent growth and lifelong development, and the COVID-19’s effects on family relationships, it reveals the importance and necessity of assessment instruments in the field of family counselling. And concerning the gap between family research and clinical practice as well as the absence of a singular tool capable of evaluating various family functions comprehensively in the Macao context, the study introduced the Basic Family Relations Inventory (BFRI; or ‘Cuestionario de Evaluación de las Relaciones Familiares Básicas’, CERFB), a self-reported questionnaire based on Linares’ Basic Family Relations Theory. This valuable tool consists of 25 items, assessing simultaneously the quality of family relationships in two basic dimensions—marital and parental functioning. This study aimed to develop the Chinese version of the BFRI and investigate its psychometric properties in the context of Macao. By employing a quantitative research approach, it evaluated the normal distribution, exploratory factor analysis and reliability of the BFRI in a non-clinical snowball and convenience sample of 165 participants with at least one biological child from 12 to 18 years old. In the exploratory factor analysis, the initial factor extraction resulted in four components, reflecting both marital and parental items. This suggested potential overlap and interconnectedness between the marital and parental subsystems. Subsequent analysis identified a three-factor solution, separating marital, negative parental, and positive parental components. This aligned with the factor structure of the original Spanish version of the BFRI. A two-factor solution was also explored, replicating findings from the previous Italian and Portuguese validation of the BFRI despite some inconsistencies in item alignment. The EFA results revealed that the three-factor structure of the Chinese version of the BFRI was the best fitting model for the Macao population. Reliability analysis, assessed through Cronbach’s alpha, indicated satisfactory internal consistency of the scales. The results of the analyses demonstrate promising psychometric properties, supporting the tool’s effectiveness in assessing marital and parental relationships in a Macao population. The study contributed to the development of the valuable family assessment instrument. It suggested that the Chinese version of the BFRI could serve as a useful instrument to concurrently assess the quality of marital and parental relationships and systematically collect the data of family functioning in both dimensions. It’s also believed that this instrument could benefit the evaluation of family dynamics and comprehension of family relations not only in family research studies, but also in counselling intervention and clinical therapy, preventing risks to the health of children as well as promoting healthy family contexts in Macao
Keywords: Basic Family Relations Inventory (BFRI); Marital relationship; Parental relationship; Psychometric properties; Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

EXPLORING MUSLIM STUDENTS LIVED EXPERIENCES IN MACAU: A PHENOMENOLOGICAL APPROACH - Ho, Kit Ieng (University of Saint Joseph, 2024)
Muslim community is one of the minority groups in Macau SAR China. Muslims are an interesting group in terms of research because of its diversity in respect to language, nationality, social status, and education level. Groups of people migrate for various reasons such as religion, politics, economy, and education. Individuals experience the age in between nineteen and twenty-four, which fall in the category of youth. Studies of Muslim youths have gained more attention in scholarship, statistical data, and research. The study seeks to understand Muslim students’ life and the needs of this minority group and explores how Muslim students perceive Islam and their own ability to cope with school related cultural pressures through qualitative, phenomenological approach, and focuses on exploring the common experiences of Muslim students in this city. This study used a conceptual framework based on critical race theory (CRT). We use in-depth interviews of five Muslim youth, ages between 19 and 24, to investigate their school life experiences and Islamic practices. We also administered questionnaires and field note to understand their social mobility, social capital and to gain a deeper understanding of their daily lives. A thematic analysis of the interview data produced the following themes: 1) Social mobility; 2) Social capital Relationship with friends; 3) Discrimination and micro-aggressions; and 4) Religion Identity. The study found that the Muslim status of the participants did not have a significant impact on their school experience, as they were able to find accommodation in their practice of religion and school life. However, the multiple identities of the participants as Macau citizens and their ethnic backgrounds did affect their social capital and sense of belonging. The study also examined the experiences of the participants within Macau society, including social factors such as racism. The results indicated that language and ethnicity were factors that hindered their integration into the community. In addition to the original themes, the analysis of the participants' stories in this research revealed two counter-narratives that challenge prevailing narratives. These counter-narratives include the deconstruction of oppressed Muslim women's narratives and the influence of local mainstream religious schooling on Muslim students' religious loyalty. These alternative narratives provide new insights into the lives of Muslim youths and challenge conventional stories. The findings of this study have important implications for educators, academics, and members of both Muslim and non-Muslim communities. By allowing youth to establish broader connections with society and increasing their motivation to participate in and contribute to the community, this study highlights the need for inclusive educational environments that support the diverse identities of students. Furthermore, the study provides young Muslims with a voice in society, empowering them to challenge dominant narratives and promote counter narratives that reflect their experiences and perspectives to meet critical race theory ethos of ongoing active struggle
Keywords: Critical Race Theory; Muslim youth; School experience; Thesis and Dissertations Master of Education (MED); University of Saint Joseph

澳門小學教師對融合教育態度之研究 =: A Study on Macao Primary School Teachers ’Attitudes towards Inclusive Education - Kwok, Siu Kam (University of Saint Joseph, 2024)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 小學教師; 澳門; 融合教育